Adsorption behaviour of tetracycline on fresh and aged Zn-modified biochar in the presence of copper: Insights into the synergistic effect and mechanism - Hua Deng; Song Lei; Shujia Chen; Xiaotong Zhou; Jiahui Fu; Pan Chen; Lening Hu; Anyu Li (Biomass and Bioenergy, 2026)

Cane water content regulates grapevine (Vitis vinifera L.) winter bud dormancy via ros homeostasis and antioxidant enzyme system - Wen-Qin Hua; Song-Yu Li; You-Mei Li; Zhao-Sen Xie (Molecular Biology Reports, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

A critical review on microalgae-driven wastewater treatment: Dual focus on high-value bioproducts recovery and emerging contaminants removal - Shuli Liu; Jiajun Hua; Yuhong Zhang; Yatong Gao; Xiaohong Han; Yali Liu; Glen T. Daigger; Qi Li; Ning Guo; Zhixin Song; Peng Zhang; Xiane Zhang; et al. (Journal of Environmental Sciences, 2026)

Engineered small extracellular vesicles–integrated multifunctional hydrogel reprograms the wound immune microenvironment for accelerated skin repair - Zhong Liu; Xinyu Zhu; Jun Cheng; Kewei Li; Yang Lou; Xiaopeng Sun; Yuhong Fan; Min Wang; Hui Qian; Yanbin Liu; Hua Ding; Song Guo; et al. (Chemical Engineering Journal, 2026)

Synergistic co‑amendment of phosphate rock and lignite improves comprehensive quality and agronomic performance of aerobic compost - Xingqun Liu; Ruyi Li; Mengyuan Song; Yune Cao; Xinxu Li; Hua Ma; Lihong Gao; Yongqiang Tian (Bioresource Technology, 2026)

Urbanization facilitates colonization and reshapes strangler-host networks: the fate of strangler figs in a tropical urban landscape and implications for management - Yu-Xuan Mo; Huang Zou; Hai-Xia Hu; Josep Peñuelas; Zhi-Peng Wang; Bang-Xiao Zheng; Xian-Meng Shi; Su Li; Sujan Balami; Hua-Zheng Lu; Liang Song (Urban Forestry & Urban Greening, 2026)

Multi-scale evolutionary forces shape the phylogeography of an Old World disjunct plant genus Girardinia (Urticaceae) - Zhi-Peng Li; Hai-Ling Qi; Fu-lv Liu; Ying Zhao; Alexandre K. Monro; Abdullah; Xiao-Yu Song; Yue-Hua Wang; Zeng-Yuan Wu; Jie Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A pH-responsive bilayer film based on PHBV/ZnO and polyvinyl alcohol/carboxymethyl konjac glucomannan/alizarin was developed for monitoring and maintaining pork freshness - Qiu-Yu Peng; Meng Wang; Song Chen; Long-Hua Zou; Yun-Cheng Li; Fan-Bing Meng (Food Chemistry, 2026)

From black box to transparency: Explainable artificial intelligence driven origin identification of Xinjiang Nilka black bee honey - Xiao-Hui Sun; Lin-Hua Shi; Xiang-Shuai Li; Xiu-Ying Tang; Hong-Song Ren; Sheng-Hong Liu (Food Chemistry, 2026)

Establishment of a novel brain cell line from grass carp (Ctenopharyngodon idella) with high transfection efficiency and CRISPR/Cas9-mediated genome editing capacity - Zi-Ling Qu; Tao Liu; Tang-Kai-Yuan Qin; Hua-Mei Yue; Ling Huang; Rui Ruan; Chang-Song Wu; Huan Ye; Chuang-Ju Li (Fish & Shellfish Immunology, 2026)

Corrigendum to “Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system” [Estuar. Coast Shelf Sci. 340 (2026) 110113] - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Phenothiazine-based self-assembled monolayer enabling high-efficiency and scalable inverted perovskite solar cells - Huilin Xie; Mingxin Wang; Xiaofeng He; Peng Wang; Miaoxin Li; Cheng Zhong; Qunliang Song; Yong Hua; Fei Wu; Linna Zhu (Chemical Engineering Journal, 2026)

Phenotypic and molecular characterization of Vibrio cholerae from aquatic products - Yao Shen; Jiangang Ma; Huafeng Jian; Shuaijie Song; Zhiyu Li; Fengcheng Miao; Xiaoqian Long; Yukun Jie; Yuchen Wang; Feng Lin; Yali Dang; Hua Yang (Journal of Invertebrate Pathology, 2026)

Activity-guided discovery of antibiotic-transforming bacteria from environmental microbiomes using D-amino acid–assisted fluorescence-activated cell sorting - Yi Liu; Kai-Li Wang; Yu-Qi Hong; Ye Yuan; Hua Wang; Yi-Qun Chen; Sheng-Song Yu; Zi-Xuan Lu; Yuan Pan; Ting-Ting Zhu (Environmental Pollution, 2026)

One-dimensional chain structure enables anisotropic hard X-ray detection in Hg2Br2 single crystal with ultralow detection limit - Lin Liu; Yunqiu Hua; Qi Li; Tao Wang; Na Lin; Zhongjie Yue; Jian Song; Zhitai Jia; Xian Zhao; Guodong Zhang; Xutang Tao (Chemical Engineering Journal, 2026)

Aberrant Gamma Oscillations in Parkinson’s Disease - Bing-Yu Li; Ruo-Yu Li; Rong-Hua Hong; Yun-Ping Song; Ling-Jing Jin (Neuroscience Bulletin, 2026)

Modeling and analysis of structural effects and detection characteristics for a new toroidal coil–excited lateral resistivity logging-while-drilling (LWD) tool - Ya-Ping Zheng; Wei Xu; Hao Li; Yong-Song Zheng; Wei-Ping Wu; Ze-Hua Yan; Xin Li; Min Liu (Applied Geophysics, 2026)

Wild Tibetan macaques employ a social sleep strategy to balance sleep needs and ecological pressures - Pei-pei Yang; Pritish Chakravarty; Wen-bo Li; Zi-tan Song; Xi Wang; Margaret C. Crofoot; Jin-hua Li (Animal Behaviour, 2026)

Divergent accumulation of particulate and mineral-associated organic carbon driven by intercropping duration in apple orchards - Rongqin Zhang; Xiaomeng Wei; Ming Li; Huike Li; Xining Zhao; Zhilong Duan; Hua Gao; Xiaolin Song (Soil and Tillage Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Wettability-switchable deep bed filtration for efficient oily wastewater treatment - Song Xichen; Yan Yaping; Zhang Tingting; Zhou Jianqiang; Wang Xiaojuan; Wang Zhezhe; Lin Jialong; Wang Ting; Song Xiaosan; Dai Liang; Wang Gang; Gao Suxia; et al. (Journal of Hazardous Materials, 2026)

Differential volatile-omics analysis for tamarind (Tamarindus indica L.) and aroma-active compounds identification via DMU-SPME-GC-MS method - Rui-Hua Jin; Ling Zhang; Li-Bo Qi; Chun-Mei Yuan; Zi-Bo Song; Jia-Teng Chen; Ming Du; Xian-Bing Xu (Food Chemistry, 2026)

Dopamine-coated LTO particles immobilized in PVA with directional dendritic channels for fast and selective lithium capture from salt-lake brines - Xunshuang Zhang; Yiming Hua; Mengyu Xie; Yihan Guo; Shilei Zhu; Yu He; Junxiang Wu; Shusen Chen; Zhou Song; Ya Nan Ye; Liangbin Li (Desalination, 2026)

Diagnosis of neurodegenerative diseases based on molecular imaging - Li Quan; Maoran Lang; Jiangtao Yue; Jiatao Zhu; Jinyao Xu; Kewei Wang; Hao Huang; Qinyong Song; Yingshi Zhao; Zhu Zhu; Chenqi Zhu; Bo Liu; et al. (Chemical Engineering Journal, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Nitrogen contents and natural 15N abundance of proteins in plants and soils: Analytical methods and biogeochemical implications - Song-Hua Li; Xue-Yan Liu (Applied Geochemistry, 2026)

A Cross-Domain Mamba Network with joint spatial-frequency learning for robust SAR oil spill detection - Pu Song; Peng Yu; Xiaojing Zhong; Lihua Wang; Yuanrong He; Guangchun Li; Zhanyang Qi; Hua Su (Marine Pollution Bulletin, 2026)

Histamine regulation in shaping spindle refractoriness: a computational modeling study - Bo Wang; Qiang Li; Wen-Hua Wang; Wan-Rong Zan; Yi-Ming Li; Jiang-Ling Song; Rui Zhang (Journal of Computational Neuroscience, 2026)

A new species and a newly recorded species of the genus Hua (Gastropoda: Semisulcospiridae) from the Chishui River, Yunnan, China - Jian-Fu Wei; Yuan-Chao Chen; Xue-Hua Li; Guang-Can Zhou; Qi-Yan Zhu; Ting-Song Yu; Jun-Xing Yang; Xiao-Ai Wang (Molluscan Research, 2026)

Crown-level, tree-only mapping of urban aboveground carbon stocks in dense city cores using deep learning - Binqiang Bao; Xin Zhang; Hao Song; Yanzheng Yang; Jalal Kassout; Xiaolu Zhou; Xuan Li; Xuan Zhao; Weihua Xu; Pengxiang Zhao; Zhiyun Ouyang; Hua Zheng (Urban Forestry & Urban Greening, 2026)

High-performance quantum interconnect between bosonic modules beyond transmission loss constraints - Hongwei Huang; Jie Zhou; Weizhou Cai; Weiting Wang; Yilong Zhou; Yunlai Zhu; Ziyue Hua; Yifang Xu; Lida Sun; Juan Song; Tang Su; Ming Li; et al. (Science Bulletin, 2026)

Corrigendum to “Phenotypic and molecular characterization of vibrio cholerae from aquatic products” [J. Invertebr. Pathol. 218 (2026) 108644] - Yao Shen; Jiangang Ma; Huafeng Jian; Shuaijie Song; Zhiyu Li; Fengcheng Miao; Xiaoqian Long; Yukun Jie; Yuchen Wang; Feng Lin; Yali Dang; Hua Yang (Journal of Invertebrate Pathology, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

Oceanic chlorine enrichment preceding end-Permian warming linked to volcanic degassing - Jing-Yi Wang; Yang Li; Hai-Jun Song; Ruo-Yu Bai; Xian-Hua Li (Geochimica et Cosmochimica Acta, 2026)

Underestimated breadth and flexibility of bacterial interactions on polysaccharide hydrolysis of Saccharophagus degradans in binary co-culture - Dao-Feng Zhang; Meng-Han Huang; Zi-Yue Li; Yu-Xin Zhang; Cheng-Song Wu; Ai Hua Zhang (Archives of Microbiology, 2026)

A calculation model on the minimum safe thickness of water-resisting rock mass for tunnel crossing active fault considering the fractal dimension and seismicity - Fan-meng Kong; Bing-hua Zhou; Xin Li; Zhao-di Han; Wen-song Wang (Applied Geophysics, 2026)

Integrated metatranscriptomic and metabolomic analyses reveal microbial succession and flavor formation pathways driven by distinct vinification strategies - Yinting Ding; Wanni Wang; Tingting Luo; Manshun Liu; Zhengwen Zhang; Yinghui Song; Hua Wang; Hongyu Zhao; Hua Li (International Journal of Food Microbiology, 2026)

Seasonal variations in nitrogen thresholds for the growth of larger and smaller phytoplankton communities in the Daya bay - Li Li; Jie Dong; Xiuchen Hua; Yu Zhong; Yifan Wang; Fei Liang; Xingyu Song; Yehui Tan; Gang Li (Estuarine, Coastal and Shelf Science, 2026)

Al3+/H+ dual-cation synergistic phosphorus-functionalized MXene aerogel for supercapacitor applications - Yan Song; Changrui Hua; Linghong Lu; Shiben Jiang; Guanyu Chu; Jun Li (Chemical Engineering Journal, 2026)

Corrigendum to “Acanthoic acid protectsagainst ethanol-induced liver injury: Possible role of AMPK activation and IRAK4 inhibition” [Toxicol. Lett. 281 (2017) 127–138] - You-Li Yao; Xin Han; Jian Song; Jing Zhang; Ya-Mei Li; Li-Hua Lian; Yan-Ling Wu; Ji-Xing Nan (Toxicology Letters, 2026)

Mechanisms of cavitation-induced instability and performance loss in bulb tubular turbines - Xiaotong Song; Zhenggui Li; Shenglong Gu; Chuang Cheng; Meng Liu; Shouchun Liu; Hang Xin; Yanxiong Jiao; Wei Hua (Ocean Engineering, 2026)

Multi-omics evaluation of grape microbial diversity and natural wine flavor metabolites under extra-simplified eco-viticulture - Yinting Ding; Wanni Wang; Tingting Luo; Yinghui Song; Yujie Gao; Zhengwen Zhang; Hongyu Zhao; Hua Wang; Hua Li (Food Chemistry, 2026)

Green manure co-application boosts arid agroecosystem sustainability: Mixed sowing of feed rape and hairy vetch modulates N input and enzymes for optimized wheat production - Ru Yu; Jie Zhou; Fangdi Chang; Jiashen Song; Jing Wang; Xiaobin Li; Hua Zhang; Jufeng Cao; Xiaohong Li; Hanjiang Liu; Hongyuan Zhang; Yuyi Li (Field Crops Research, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Nutrient accumulation and redox conditions shape lake bacterial communities: A dual-medium assessment of closed coal-mining subsidence versus natural lakes - Shuo Li; Lei Zhang; Wen Ge; Yijie An; Ting Song; Feng Xu; Hua Cai (Journal of Environmental Chemical Engineering, 2026)

Bioinspired composite aerogel with hydrophobic-hydrophilic patterned wettability for high-efficiency, salt-resistant solar desalination - Linfan Li; Bopeng Li; Hua Li; Yumin Wang; Xiao Miao; Yuanming Song; Guina Ren; Xiaotao Zhu (Journal of Environmental Chemical Engineering, 2026)

Mechanism-driven immobilization of manganese and cadmium by potassium-activated biochar: Insights into the potential mechanisms - Hua Deng; Shuyun Zhang; Feng Jiang; Song Lei; Shujia Chen; Xiaotong Zhou; Lening Hu; Anyu Li (Journal of Environmental Chemical Engineering, 2026)

Efficient pollutant removal by iron-carbon bioretention system in long-term operation: Stability and performance - Zhou Jianqiang; Song Xichen; Wang Xiaojuan; He Jiangtao; Zhou Yawen; Qin Jie; Xiao Yifei; Gao Suxia; Li Hua; Liu Jianlin; Li Wei; Cao Lianbao; et al. (Journal of Environmental Chemical Engineering, 2026)

Fermented red quinoa (FRQ) effectively mitigates chronic alcohol-induced cognitive impairment and hepatic steatosis through multi-mechanistic pathways - Zi-Han Lin; Zhaohui Wang; FenFen Wei; Xinyao Zhu; Junwei Ma; Yan Wu; Song-Mei Chen; Li-Hua Song (Food Research International, 2026)

Revealing the metabolic mechanism of enzymatic hydrolysis products of boletus edulis bull.: Fr. Based on random forest integration multi-omics - Ningjing Guo; Xiang Li; Ya Dai; Xue Li; Qian Yao; Hua Lin; Mingjing Song (Food Chemistry, 2026)

Mechanistic insights into how wheat flour mill streams affect Chinese steamed bread quality: A perspective from starch multi-scale structure and physicochemical properties - Mengkun Song; Yongji Ni; Junhui Gao; Xiangjie Li; Yingying Zhang; Yanyan Zhang; Xingli Liu; Huishan Shen; Hua Zhang; Hongwei Wang (Carbohydrate Polymers, 2026)

Dietary Formic Acid Supplementation Affects the Growth and Health Status and Alters the Gut Transcriptome and Microbiota in Largemouth Bass (Micropterus salmoides) - Zelin Huang; Chuanbo Xiao; Xia Liu; Junwa Huang; Lv Song; Shenfu Zhao; Dan Yang; Hujun Gao; Zhenlin Ke; Yuxiao Li; Lihua Yang; Hua Ye; et al. (Marine Biotechnology, 2026)

The Strawberry C2H2 Zinc Finger Protein FvZFP57 Positively Regulates Drought Stress - Shou-bing Chen; Zhi-kai Song; Jian Guo; Ming-di Yang; Shuai-jie Li; Ming-li Zhu; Junxiang Yu; Meng Xu; Yi-hua Liu (Journal of Plant Growth Regulation, 2026)

A deprotection-oxidation cascade-regulated dual-responsive near-infrared fluorescent probe for individual and sequential detection of H2S/HClO with applications in food safety monitoring - Jie Yang; Chao Fu; Yicong Zhou; Hua Zhang; Xiangzhi Song; Dandan Li; Chuanxiang Liu (Analytica Chimica Acta, 2026)

Isolation and biological evaluation of a novel steroid from Sagina japonica (Sw. ex Steud.) Ohwi - Jun-Hong Liu; Qian-Lian Yin; Xue Li; Mei Qing Zhang; Lin Guo Zou; Xin Jian Song; Li Jiang; Chun Hua Liu; Yong Jun Li (Natural Product Research, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

Active and passive co-observations from a spaceborne lidar: Retrieving surface reflectance and aerosol optical thickness using ICESat-2 signal and noise data - Jian Yang; Huiying Zheng; Yue Ma; Xinyuan Liu; Song Li; Xiao Hua Wang; Wei Gong (Remote Sensing of Environment, 2026)

Comprehensive multi-omics integration analysis identifies the functional association between linoleic acid and meat quality variation among different cattle breeds - Jiapeng Wang; Lishuang Song; Hua Du; Yingxu Shi; Shuyu Zhang; Qianqi Sun; Wenshuo Gao; Fuxia Han; Xinru Li; Shengtao Gao (Food Chemistry, 2026)

Investigation of electron beam irradiation in inhibiting retrogradation behavior of mung bean starch gel - Huishan Shen; Jiaqi Wang; Xinhui Li; Keshi Yang; Min Li; Yanyan Zhang; Xingli Liu; Mengkun Song; Hongwei Wang; Hua Zhang (Food Hydrocolloids, 2026)

Deciphering how starch hierarchical structure and flour technological properties affect the quality attributes of glutinous dumplings - Hongwei Wang; Yuhan Zhang; Mengyuan Jia; Xiaojuan Yang; Yanyan Zhang; Mengkun Song; Xingli Liu; Min Li; Hua Zhang; Huishan Shen (Food Hydrocolloids, 2026)

Flexible thiol–ene crosslinked reduced graphene oxide-functionalized styrene-butadiene-styrene films with enhanced thermal conductivity and electromagnetic interference shielding efficiency - Xinyu Liu; Xiaohui Lv; Chuang Peng; Linzhe He; Yibo Zhang; Song Lei; Guo-Hua Hu; Zhehong Lu; Tao Ding; Xiaohong Li; Zhijun Zhang (Chemical Engineering Journal, 2026)

Experimental and Theoretical Investigations of Fatigue Mechanical Behavior of Transversely Isotropic Composite Rocks - Yu Song; Sheng-Qi Yang; Xiang-Xi Meng; Ke-Sheng Li; Yan-Hua Huang; Li-Feng Fan (Rock Mechanics and Rock Engineering, 2026)

Seismic Data Reconstruction and Noise Suppression Based on an Improved Weighted Fast Projection onto Convex Sets Algorithm - Gao-peng Cheng; Hua Zhang; Hong-xing Li; Yu Song; Ming Yue; Kai-dong Zhang (Applied Geophysics, 2026)

Rethinking trophic transfer efficiency in freshwater ecosystems: Current understanding and knowledge gaps - Hua Song; Fen Guo; David Dudgeon; Xiaoguang Ouyang; Feilong Li; Siyong Wu; Zhenmin Yang; Wei Gao; Yuan Zhang; Stuart E. Bunn (Limnology and Oceanography, 2026)
Trophic transfer efficiency (TTE) represents the proportion of energy transferred between consecutive trophic levels within a food web. Though it is a fundamental property that shapes energy flow across all ecosystem types, a comprehensive understanding of TTE in freshwater ecosystems is still lacking. This review evaluated common estimation methods, identified key influencing factors, and outlined future research priorities based on a global freshwater TTE dataset. Methods to estimate TTE include production estimates, carbon‐transfer measurements, model‐based approaches, and predator–prey mass‐ratio estimates; mixed‐effects analyses indicate that method choice significantly structures reported TTE, yet each method has limitations in accuracy and consistency. Trophic transfer efficiency also varies across ecosystem types, consistent with systematic differences in the environmental and biological controls on energy transfer among systems. Light, nutrients, and organic matter affect TTE by altering the abundance and composition of primary producers, whereas food quality, temperature, and dissolved oxygen impact TTE by modulating consumer growth and metabolism of individual consumers. At the community and ecosystem levels, predation pressure, competition, species richness, the presence of non‐native species, and cross‐ecosystem interactions shape community structure, thus affecting TTE. Better understanding of TTE in freshwater ecosystems will depend on refined estimation methods and integration of new techniques, such as remote sensing and stable‐isotope labeling, to improve TTE estimates. Research priorities include understanding the synergistic effects of anthropogenic pressures and climate change on TTE, investigating how food quality and individual‐level metabolic processes govern TTE, and examining the influence of cross‐ecosystem energy fluxes on TTE dynamics. It is essential to recognize that TTE varies among trophic levels and cannot be represented by a single value along the entire food chain. Our synthesis reveals that more research is needed in the tropics and the southern hemisphere to expand our understanding of global variability in TTE. This would facilitate greater use of TTE as an indicator of ecological change or the restoration of efficient energy transfer through freshwater food webs.

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

A single-cell-resolution spatial transcriptomic atlas decodes wheat spike development and yield potential - Xiang Zhang; Yi Peng Wang; Xiehai Song; Liang-Zi Zhou; Haixia Yu; Lei Yang; Yan Kai Wang; Xin Yu Wang; Xin Yan Wan; Yongqi Liu; Yan Shi; Zhiliang Yue; et al. (Molecular Plant, 2026)

Different expansion events of the actin and tubulin gene families within spirotrichean ciliates (Alveolate, Ciliophora) - Hua Su; Zengyu Song; Guoling Chai; Fangfang He; Yize Li; Yuxuan Qian; Xuefen Lu; Qi Zhang; Zhenzhen Yi (Molecular Phylogenetics and Evolution, 2026)

Biomimetic rehabilitation of damaged contaminant-containment and load-bearing structure by a near-zero disturbance method: Pilot-scale test in an operating plant - Ya-song Feng; Shui Wang; Yu-tao Chen; Meng-ya Li; Zhi-hua Yin; Zong-xiang Lv (Journal of Cleaner Production, 2026)

Lactic acid modulates empty-cup aroma persistence in Baijiu via molecular interaction mechanisms: a case study of strong-aroma and soy-sauce-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Xiao-Juan Zhang; Zheng-Juan Zhu; Ru-Yi Li; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Guan-Yu Fang; Qing-Qing Liu; Yong-Jun Yuan; et al. (Food Chemistry, 2026)

Enhancing oil-water separation via droplet coalescence regulated by particle self-rotation in swirling fields - Wei Zhao; Ao-song Wei; Shu Zhu; Tong Zhang; Peng-bo Fu; Jian-ping Li; Xue-jing Yang; Hua-lin Wang (Water Research, 2026)

Efficient decomplexation of Cu(II) complexes and Cu(II) recovery via one-step Fenton-like oxidation/adsorption processes mediated by nanoconfined hydrous Co-Zr oxides - Xin Li; Xuewei Song; Lu Lv; Weiming Zhang; Bingcai Pan; Ming Hua (Water Research, 2026)

Mild preheating-induced myosin supramolecular hydrogels: A thermoresponsive food material with reversibility and plasticity - Li Hu; Shuyi Song; Ruibang Zhang; Yanwei Zhang; Zhichao Xiao; Jun-Hua Shao (Food Chemistry, 2026)

Potential role of autumn sea ice over the Chukchi-Beaufort Seas in the interannual variability of spring Asian-Pacific Oscillation - Yujia Liu; Botao Zhou; Peilin Li; Wenxin Xie; Ziyi Song; Hua Li; Tingting Han (Atmospheric Research, 2026)

Single-Cell RNA Sequencing Reveals Impaired CHIP-Mediated Heat Stress Response in SCA3 Pathogenesis - Mi-bo Tang; Shi-feng Sheng; Zheng-wei Hu; Hai-yang Luo; Meng-jie Li; Shuo Zhang; Xiao-yan Hao; Cheng-yuan Mao; Shao-hua Li; Hui-fang Sun; Zhi-hua Yang; Yi Song; et al. (Molecular Neurobiology, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

Fast estimation of the carbon footprint for shipbuilding based on compensated gross tonnage - Wen-Cai Tang; De-Ning Song; Jing-Hua Li; Yu-Guang Zhong (Regional Studies in Marine Science, 2025)

Metallothionein 2A alleviates ulcerative colitis by inhibiting ferroptosis in intestinal epithelial cells with Tfrc downregulation - Siqi Hua; Shuangshuang Song; Chunhao Yang; Jingwen Xu; Zhonghua Li; Bo Zhu; Zichun Hua (Journal of Trace Elements in Medicine and Biology, 2025)

Landscape aggregation enhances soil conservation service: Insights from the grain for green program on the Loess Plateau - Dingyue Yan; Yanzheng Yang; Hao Song; Yiru Yue; Xingwu Duan; Jalal Kassout; Liming Wang; Ruonan Li; Hua Zheng (Journal of Environmental Management, 2025)

Biochar alleviates ammonium-induced suppression of methane uptake in a subtropical forest soil - Jiashu Zhou; Yanfei Dong; Caixian Tang; Zhenhui Jiang; Xinzhang Song; Mouliang Xiao; Hua Qin; Yunying Fang; Xiaokai Zhang; Tida Ge; Yu Luo; Shuokang Liu; et al. (Chemical Engineering Journal, 2025)

Humic–metal complexes as dominant anaerobic digestion inhibitor: Multidimensional diagnostic framework for 16,200-tonne full-scale sludge treatment plant - Qi Song; Yongbo Yu; Xiankai Wang; Zhengtong Tan; Feng Liu; Manyu Wang; Jiachang Cao; Yan Li; Yu Hua; Xiaohu Dai (Bioresource Technology, 2025)

Correction: Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

The Pilot Study on the Histological and Ultrastructural Characteristics of Major Immune Organs (Spleen, Head Kidney, and Trunk Kidney) and Analysis of Pathological Features in Sichuan Taimen ( Hucho bleekeri ) - Qinyao Wei; Hua Li; Yeyu Chen; Zhao Liu; Yanling Chen; Yi Yu; Quanyu Tu; Guiliang Liu; Zhaobin Song; Jun Du; Huanchao Yang (Journal of Fish Diseases, 2025)
Sichuan taimen ( Hucho bleekeri ) is a glacial relict and critically endangered fish species restricted to the Yangtze River drainage in China. The lack of knowledge regarding the morphology of immune organs may limit the timely detection of health threats, thereby hindering effective conservation efforts. To address this gap, the pilot study provides the first histological and ultrastructural characterisation of the main immune organs (spleen, head kidney, and trunk kidney) of H. bleekeri . The spleen comprises red and white pulp; the red pulp is abundant in erythrocytes, while the white pulp contains leukocytes within a reticular network. Melano‐macrophage centers, involved in immune and phagocytic activities, are prominent in the spleen and kidneys. The head kidney functions as a primary haematopoietic organ, exhibiting distinct lymphoid and non‐lymphoid zones supported by a reticular framework. The trunk kidney serves an excretory role, and its tissue contains dispersed renal corpuscles. Ultrastructural analyses revealed typical cellular features, including well‐developed rough endoplasmic reticulum and melano‐macrophage‐associated lysosomes. Notably, structural abnormalities—including mitochondrial swelling, cristae fragmentation, and mild dilation of the rough endoplasmic reticulum—were observed in the head kidney; these may potentially reflect early immune activation or sublethal environmental stress. These baseline findings would provide critical morphological references and lay a foundation for future studies on immune function, disease pathology, and conservation strategies in H. bleekeri .

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Cyanoalanine Synthase encoding gene SlCAS1 regulates tomato fruit ripening by modulating pigment metabolism and ethylene biosynthesis - Song-Li Han; Yu-Qi Zhao; Li-Xia Li; Pedro Garcia-Caparros; Yan-Hong Li; Zhen Wang; Yi-Ang Feng; Kang-Di Hu; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2025)

Multiplex immunochromatographic assay for simultaneous detection of triclosan, triclocarban and chlorophene in environmental samples - Jiaxun Li; Lingling Guo; Shanshan Song; Rui Gao; Hua Kuang; Chuanlai Xu; Liguang Xu (Journal of Hazardous Materials, 2025)

Straw mulching optimized the root and canopy structure of soybean by reducing the topsoil temperature before blooming period - Zongsheng Wu; Yupeng Zhu; Qirui Li; Ruidong Li; Simon Willcock; Viktória Vona; Robert Dunn; András Vér; Yifan Xu; Jianxin Hua; Cailong Xu; Wenwen Song; et al. (Field Crops Research, 2025)

Volatile organic compounds in various workplaces and during commutes in a Chinese city: occurrence and health risks for different occupations - Jin-Long Mai; Yi Yang; Yuan Zeng; Song Liu; Zhen-Shan Huang; Jia-Hua Wu; Ya-Jing Li; She-Jun Chen (Environmental Research, 2025)

Exploring the Effects of Different Fillers on the Treatment of Wastewater by SBBR System: Denitrification Efficiency and Microbial Community - Shuli Liu; Xiaohong Han; Miao Zhou; Yatong Gao; Yuhong Zhang; Qi Li; Ning Guo; Jiajun Hua; Jia Kang; Gangfu Song (Water, Air, & Soil Pollution, 2025)

Oxymatrine possibly inhibits differentiation and maturation of oligodendrocytes in the remyelination of the toxin-induced demyelination animal model - Mei Li; Fei Huang; Jian Song; Renzhang Liang; Zhongwei Zhou; Yinglan Lin; Lili Hu; Jinghai Gu; Hua Yang; Shaozhang Hou; Huisheng Ma; Peng Wang (Metabolic Brain Disease, 2025)

Effects of β-hydroxy-β-methylbutyrate inclusion on growth performance and fillet quality of olive flounder Paralichthys olivaceus fed low fishmeal based diets - Chaoqing Wei; Zhenxia Su; Cancan Xia; Lu Li; Zhicheng Song; Hua Mu; Hanliang Cheng; Jianhe Xu; Zhiguo Dong; Binlun Yan; Lu Zhang (Aquaculture, 2025)

Antibiotic resistance genes in multi-matrices of Chaohu Lake: Spatiotemporal variation and correlation with pesticides and PPCPs - Hao Yang; Hongwei Fu; Yutong Zhao; Run Li; Man Cao; Yi Liu; Yachao Ni; Wei Song; Yangyang Liang; Panyuan Cai; Wei Chang; Fangbiao Tao; et al. (Journal of Hazardous Materials, 2025)

Synergistic catalytic performance of toluene degradation based on non-thermal plasma with Pt-TiO2 - Yanna Liu; Wenping Li; Ali Omidkar; Zhaofei Li; Hua Song (Journal of Environmental Chemical Engineering, 2025)

Machine-learning enabled non-catalytic plasma driven route to toluene degradation and environmental impact assessment studies - Alex Liu; Yanna Liu; Wenping Li; Zhaofei Li; Hua Song (Journal of Environmental Chemical Engineering, 2025)

Dietary supplementation with Codonopsis pilosula agro-waste improves yak meat quality by enhancing oxidative stability and balancing energy metabolism efficiency during postmortem - Xue Yang; Yiheng Li; Ruheng Shen; Yufeng Duan; Rende Song; Xinjun Zhang; Hongmei Shi; Xiangying Kong; Yongli Hua; Li Zhang (Food Research International, 2025)

Protective effect of yak yogurt derived Lactiplantibacillus plantarum DACNJS22 fermented milk on DSS-induced colitis: Insights from in vitro and in vivo studies - Yu-Hang Jiang; Yang-You Li; Wei-Gang Xin; Jia-Jia Song; Chen Wang; Hua-Yi Suo (Food Research International, 2025)

Achieve high dielectric energy storage efficiency and good temperature stability within a wide range by high-entropy induced relaxor enhancement strategy in NBT-based ceramics - Jiayi Ji; Can Tian; Haiping Tang; Haikui Song; Yuan Zhou; Shaofei Zhang; Jinfeng Sun; Hua Tan; Haibo Zhang; Li Jin; Jingsong Liu; Gang Liu; et al. (Chemical Engineering Journal, 2025)

Hierarchically shortened b-axis ZSM-5 nanosheet endows super catalytic stability for methanol-to-hydrocarbons reaction - Zhan Liu; Ying-Jun He; Zhi-Yi Hu; Jia-Min Lyu; Shen Yu; Yu-Hang Song; Xiao-Qiang Liao; Zhi-Wen Yin; Ming-Hui Sun; Yu-Chun Zhi; Li-Hua Chen; Bao-Lian Su (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Proteome Profiling of Serum Reveals Pathological Mechanisms and Biomarker Candidates for Cerebral Small Vessel Disease - Yun-chao Wang; Hang-hang Zhu; Liu-Chang He; Ya-ting Yao; Lei Zhang; Xin-li Xue; Jing-yi Li; Li Zhang; Bo Song; Chang-he Shi; Yu-sheng Li; Yuan Gao; et al. (Translational Stroke Research, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Subsurface organic ameliorant is beneficial in reducing inorganic carbon loss and improving carbon sequestration in saline soils - Ru Yu; Jiashen Song; Jie Zhou; Fangdi Chang; Xiaobin Li; Jing Wang; Haoruo Li; Xia Zhang; Hua Zhang; Yuexin Zhang; Hongyuan Zhang; Yuyi Li (Applied Soil Ecology, 2025)

First total synthesis of (±)-sanggenon F and its osteogenic differentiation promoting activity on human mesenchymal stem cells - Ren-Fen Ma; Yue Jing; Hui Song; Bin Wang; Jian Li; Xiu-Shan Yin; Hua Zhang (Natural Product Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Efficient recovery of spent catalysts in PAO production via annular drainage hydrocyclone: a sustainable approach for fluorinated waste reduction - Wei Zhao; Jian-ping Li; Tong Zhang; Shu Zhu; Ao-song Wei; Dan-hui Yang; Xue-jing Yang; Hua-lin Wang (Journal of Cleaner Production, 2025)

Size-dependent diversity and accumulation of isoquinoline alkaloids in Corydalis yanhusuo tubers - Feng Jin; Honghong Jiao; Zhongxin Song; Mengyuan Zhang; Bo Li; Zhongyi Hua; Tianrui Liu; Pengjie Han; Zhishu Tang (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Coffee mitigated cognitive impairments in sleep-deprived mice by regulating circadian rhythm, inflammation, oxidative stress, and intestinal ecology - Hui-Bin Jiang; Fen-Fen Wei; Wen-Ting Li; Zi-Han Lin; Chuang Zhu; Yan Wu; Ying Wang; Li-Hua Song (Food Bioscience, 2025)

Bioinspired neural network-enabled metre-scale attached ultraductile cementitious nanosensors with temperature-immune - Hua Fu; Penggang Wang; Heping Zheng; Bo Pang; Zuquan Jin; Xiaoyun Song; Li Tian; Zhenxing Du; Bukhari Mohd Nadeem; Peng Zhang; Zhengkai Hu (Chemical Engineering Journal, 2025)

Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Characterization of novel bacteriophage as a promising alternative for controlling Vibrio infections in shrimp - Hua Xu; Wenxin Li; Yijing Zhang; Mingxu Li; Xuan Dong; Song Zhang; Jie Huang; Juhee Ahn (Aquaculture, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Characterization of desalting wastewater: Stability and demulsification mechanisms - Hua Zhang; Zhansheng Wang; Jufeng Li; Mingxuan Li; Zejun Zhang; Jiayu Song; Yilin Wang (Journal of Water Process Engineering, 2025)

Recent advances on electrically controlled solid propellants - Yang Li; Hong-Yu Lv; Si-Wei Song; Qi-Long Yan; Qing-Hua Zhang (Fuel, 2025)

Multidimensional impacts of ocean alkalinity enhancement on aquatic ecosystems and fisheries carbon sequestration capacity - Chang Liu; Chengzhuang Chen; Ying Wang; Mingxing Zhang; Xihong Song; Ling Liu; Ping Li; Zhi-Hua Li (Environmental Impact Assessment Review, 2025)

Salidroside alleviates cardiomyocyte senescence by activating the AMPK-mediated signaling pathway - Lan Zhang; Yawei Liu; Zhijuan Hua; Yan Qin; Tao Wang; Na Li; Lei Song (Journal of Molecular Histology, 2025)

Bioinformatic Analysis of the Significance of the KIR2DL4 Gene in Recurrent Implantation Failure - Xin-Xian Zhang; Zhi-Chao Zhang; Yu-Shan Liu; Li Zhou; Yu-Qin Hu; Cai-Hong Zhang; Wen-Hui Song; Xiao-Hua Wu (Biochemical Genetics, 2025)

Model test on dynamic response of coral sand in island dredging airport under wave, tidal and aircraft landing load - Jianxiu Wang; Ansheng Cao; Dongsheng Song; Bo Feng; Hua Zhang; Huboqiang Li; Yanxia Long; Zhenhua Ye (Marine Georesources & Geotechnology, 2025)

Machine learning-driven simultaneous quantification of Cd(II) and Cu(II) on Co2P/CoP heterostructure: enhanced electrochemical signals via activated Co-P electron bridge - Zhi-Wei Gao; Yan Yu; Shi-Hua Chen; Yong-Yu Li; Zi-Hao Liu; Meng Yang; Pei-Hua Li; Zong-Yin Song; Xing-Jiu Huang (Journal of Hazardous Materials, 2025)

The synergistic effects of oleogelators based on different structuring mechanisms: A viable way to tailor oleogels with ideal thermo-responsiveness and rheological properties - Li Hu; Ruibang Zhang; Shuyi Song; Zongyuan Han; Zhichao Xiao; Jun-Hua Shao (Food Chemistry, 2025)

Development and evaluation of recombinant multi-epitopes vaccine against nervous necrosis virus - Chen Zhang; Wei-Nan Zhao; Xin-Xin Liu; Wen-Ye Song; Hai-Hua Peng; Min Yang; Peng-Fei Li; Jin-Qi Wei; Yong-Can Zhou; Yun Sun (Fish & Shellfish Immunology, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Research on all-day water vapour profile retrieval method based on lidar data and machine learning algorithm - Xiao Cheng; Huige Di; Qimeng Li; Ning Chen; Jiaying Yang; Kai Song; Dengxin Hua (International Journal of Remote Sensing, 2025)

Incidence, risk factors, and prognosis of hospitalized mechanical eye injuries in China: data from China Ocular Trauma Study (COTS) 2021–2023 - Han Han; Yongjie Chen; Gao Si; Guowei Huang; Jiayi Song; Wenfang Zhang; Danyan Liu; Jie Zhong; Xuemin Jin; Dawei Sun; Shenwen Liu; Yanming Huang; et al. (Science Bulletin, 2025)

Seasonal and regional differences of heavy metals and nutrients from the five mariculture areas of large yellow croaker: Implications for environmental and fish quality - Yong-Long Chen; Fa-Guo Wan; Qing-Hao Zhan; Jia-Lang Zheng; Tian-Hong Chen; Shang-Wei Xie; Li-Hua Jiang; Shun Chen; Qing-Ling Zhu; Wei-Hua Song; Xiao-Jun Yan (Environmental Pollution, 2025)

Flexible, scalable, and bifunctional MOF-based nanofibrous membranes with gems-on-string structure for simultaneous efficient water evaporation and pollution remediation - Song Ge; Jun Song; Jichao Zhang; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2025)

Exploring the role of biological soil crusts in protecting rammed earth sites: A case study of the Shanhaiguan Great Wall in Bohai Bay - Liang Liu; Yun Zhang; Lingling Zheng; Lianjun Guo; Tianli Li; Lirong Song; Hua Li; Haiying Cao; Dongdong Li (Plant and Soil, 2025)

Regeneration and Agrobacterium-mediated genetic transformation in Allium senescens L - Xue Song; Yi Hua; Chuhan Fu; Jiahong Li; Haotian Li; Xuetong Sun; Jingjing Qi; Ligang Qin (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Distinct evolutionary origins and mixed-mode transmissions of methanogenic endosymbionts are revealed in anaerobic ciliated protists - Tingting Hao; Hua Su; Zijing Quan; Ruixin Zhang; Minjie Yu; Jiahui Xu; Jia Li; Song Li; Alan Warren; Saleh A. Al-Farraj; Zhenzhen Yi (Marine Life Science & Technology, 2025)
Methanogenic endosymbionts are the only known intracellular archaeans and are especially common in anaerobic ciliated protists. Studies on the evolution of associations between anaerobic ciliates and their methanogenic endosymbionts offer an excellent opportunity to broaden our knowledge about symbiosis theory and adaptation of eukaryotes to anoxic environments. Here, the diversity of methanogenic endosymbionts was analyzed with the addition of nine anaerobic ciliate populations that were newly studied by various methods. Results showed that diverse anaerobic ciliates host methanogenic endosymbionts that are limited to a few genera in orders Methanomicrobiales, Methanobacteriales, and Methanosarcinales. For the first time, anaerobic ciliates of the classes Muranotrichea and Prostomatea were found to host methanogenic endosymbionts. Distinct origins of endosymbiosis were revealed for classes Armophorea and Plagiopylea. We posit that armophoreans and plagiopyleans might have harbored Methanoregula (order Methanomicrobiales) and Methanocorpusculum (order Methanomicrobiales), respectively, as methanogenic endosymbionts at the beginning of their evolution. Subsequently, independent endosymbiont replacement events occurred in methanogen-ciliate associations, probably due to ecological transitions, species radiation of ciliate hosts, and vertical transmission bottlenecks of endosymbionts. Our results shed light on the evolution of associations between anaerobic ciliates and methanogens, and identifies the necessary preconditions for illustrating mechanisms by which endosymbioses between these partners were established.

Cytotoxic metabolites from the mangrove endophytic fungus Aspergillus sp. GXNU QG1a - Xianglong Bo; Yufei Zhao; Feng Qin; Furong Wu; Meijing Tan; Shichao Ju; Zishuo Song; Wenjun Li; Fan He; Youquan Wei; Hua Xu; Xishan Huang (Natural Product Research, 2025)

Tracking of single virus: Dual fluorescent labeling of pseudorabies virus for observing entry and replication in the N2a cells - Mingzhi Li; Li Pan; Caoyuan Ma; Hongxia Wu; Guangtao Xiang; Lian-Feng Li; Tao Wang; Rui Luo; Yongfeng Li; Di Liu; Huanjie Zhai; Moon Assad; et al. (Veterinary Microbiology, 2025)

Comparative analysis of virulence in Listeria monocytogenes: Insights from genomic variations and in vitro cell-based studies - Yiyang Song; Binru Gao; Hua Cai; XiaoJie Qin; XueJuan Xia; Qingli Dong; Takashi Hirata; Zhuosi Li (International Journal of Food Microbiology, 2025)

Deuteration solid additive strategy for high-performance and thermally robust organic solar cells - Bowen Li; Hao Xia; Ruijie Ma; Yujia Zhang; Tian Zhu; Yongxiang Liu; Shangmin Chu; Mengbing Zhu; Xin Song; Hua Tan; Weiguo Zhu (Chemical Engineering Journal, 2025)

Organic-phosphate hybrids with colorful persistent luminescence - Tuo-Yu Zhou; Qian Zhao; Hong-Yu Zhao; Chang Li; Fang-Yuan Zeng; Jingjing Zhou; Jiuyuan Li; Yujiao Wang; Guang-Yue Li; Yuejuan Liang; Yanmin Song; Sheng-Hua Li (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Multifaceted Precipitation Patterns Impact Biocrust Functionality in Drylands: A Cascade of Variability via Species Replacement in Soil Microbiota - Xiaoyu Guo; Zuowen Wang; Hua Li; Haijian Yang; Weibo Wang; Lirong Song; Chunxiang Hu (Global Ecology and Biogeography, 2025)
Aim The influences of climatic gradients on biodiversity and functionality in arid ecosystems are increasingly evident. While soil microbes are susceptible to precipitation patterns, the mechanisms through which their variations affect the delivery of multiple ecosystem functions via microbial communities are poorly understood. Here, we examined the direct effect of precipitation gradients on multifunctionality and the indirect effect mediated by soil microorganisms and edaphic properties in drylands. Location Northwestern China. Time Period Field investigation in 2020. Major Taxa Studied Multitrophic microbiota in biocrusts. Methods We analysed 38 years of daily precipitation data to quantify multifaceted characteristics and spatial variations, including gradients of mean amount, frequency, and variability. Community structures of heterotrophic bacteria, fungi, and photoautotrophic cyanobacteria were determined via amplicon sequencing to measure taxonomic and phylogenetic α ‐diversity and spatial turnover. Local multifunctional levels ( α ‐multifunctionality) and their pairwise dissimilarity/asynchrony ( β ‐multifunctionality) were depicted based on functional variables related to biocrusts. We investigated how precipitation and microbial diversity jointly influence soil multifunctionality. Results We found historical precipitation variability, rather than mean annual precipitation, emerged as the primary driver promoting functional variance, leading to a convergence of less beneficial microbial species under high precipitation fluctuations. Although species richness across trophic levels positively influenced local functions, phylogenetic dissimilarity was a key predictor for soil photoautotrophs. As a β ‐diversity component, species replacement consistently enhanced multifunctional dissimilarity and asynchrony of biocrusts. Notably, a cascading process was identified where the indirect effect of precipitation heterogeneity, regulated by microbial β ‐diversity, accounted for a higher proportion of variance in β ‐multifunctionality than direct climate influence. Main Conclusions This study highlights the importance of precipitation variability and indirect climate impact mediated by soil microbiota. It contributes to a deeper understanding of the real‐world consequences of altered precipitation on drylands, providing valuable insights for interventions to mitigate climatic perturbations by managing soil community properties.

Penicipyrrolidines A−N, pyrrolidine derivatives with inhibitory effects on EMT and fibroblast activation from the mangrove-derived fungus Penicillium sp. DM27 - Li-Ming He; Xuan Deng; Li-Hua Ni; Shi-Qi Cai; Jinhu Chen; Zejin Liao; Mengke Zhang; Hua Shui; Kong-Kai Zhu; Song Wu; Ping Gao; Ariel M. Sarotti; et al. (Marine Life Science & Technology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Late Pliocene evolution of hydroclimate, temperature and ecosystem in the Tianshui Basin, northeastern Tibetan Plateau, China: A multiproxy geochemical approach - Tingjiang Peng; Xiaomiao Li; Hui Hua; Zhenzhong Tian; Mingqiu Zhang; Meng Li; Zhenhua Ma; Benhong Guo; Jia Liu; Zhantao Feng; Zhijun Zhao; Chunhui Song (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Octahedral copper metal-organic framework grafted with MoS2 nanoflowers for high-performance oxygen reduction reaction - Cong Li; Zhi Song; Hua Liu (Journal of Environmental Chemical Engineering, 2025)

Colloidal gold immunochromatographic assay for the detection of total aflatoxins in cereals - Xiaofang Li; Liqiang Liu; Shanshan Song; Maozhong Sun; Hua Kuang; Chuanlai Xu; Lingling Guo (Food Chemistry, 2025)

New insights into the tenderization pattern of yak meat by ROS-ERS: Promotion of ERS-associated apoptosis through feedback regulation of PERK/IRE1/ATF6 and caspase-12 activity - Xue Yang; Yiheng Li; Ruheng Shen; Rende Song; Yufeng Duan; Xinjun Zhang; Hongmei Shi; Xiangying Kong; Yongli Hua; Li Zhang (Food Chemistry, 2025)

Synergistic protective effects of probiotics Lactiplantibacillus plantarum S58 and prebiotics Qingke β-glucan on dextran sulfate sodium-induced cognitive deficits in colitis mice: A study of microbial-gut-brain axis modulation - Yu-Hang Jiang; Jia-Xin Zhao; Yang-You Li; Wei-Gang Xin; Jia-Jia Song; Xiao-Yong Chen; Chen Wang; Hua-Yi Suo (Food Bioscience, 2025)

Colloidal gold-based immunochromatographic assay for the detection of carmoisine in soft drinks - Xiaoling Li; Lingling Guo; Shanshan Song; Liqiang Liu; Hua Kuang; Chuanlai Xu; Xinxin Xu; Liguang Xu (Food Bioscience, 2025)

Correction: Inhibition of 12/15 lipoxygenase by baicalein reduces myocardial ischemia/reperfusion injury via modulation of multiple signaling pathways - Lina Song; Hui Yang; Hong-Xia Wang; Cui Tian; Yu Liu; Xiang-Jun Zeng; Erhe Gao; Yu-Ming Kang; Jie Du; Hui-Hua Li (Apoptosis, 2025)

Luteolin ameliorates ischemic/reperfusion injury by inhibiting ferroptosis - Hua Li; Jin-xia Li; Yi-di Zeng; Cai-xing Zheng; Si-si Dai; Jian Yi; Xu-dong Song; Ting Liu; Wang-hua Liu (Metabolic Brain Disease, 2025)

Allograft valves harvesting and preservation technique for enhanced performance - Congrui Wang; Xiumeng Hua; Qiuju Li; Shun Liu; Hao Jia; Hao Cui; Ningning Zhang; Zeyu Cui; Yuan Chang; Mengni Bao; Han Mo; Zhe Sun; et al. (Cell and Tissue Banking, 2025)

Exploring eutrophic effects of marine sediments underneath fish cage farms: Insights from changes in eukaryotic and bacterial communities and volatile organic compounds - Fa-Guo Wan; Yong-Long Chen; Jia-Lang Zheng; Wang-Yang Jin; Tian-Hong Chen; Qing-Ling Zhu; Qing-Hao Zhan; Li-Hua Jiang; Shun Chen; Wei-Hua Song; Xiao-Jun Yan (Science of The Total Environment, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Spatial distribution of bacteria in response to phytoplankton community and multiple environmental factors in surface waters in Sanggou Bay - Song Peng; Rong Bi; Jiwen Liu; Jiaxuan Cui; Xinkai Fu; Xiaotong Xiao; Ruihuan Li; Zengjie Jiang; Shulan Xu; Chuanli Zhang; Xiao-Hua Zhang; Meixun Zhao (Marine Environmental Research, 2025)

Petrogenesis and geodynamic mechanism of Early Miocene post-collisional ultrapotassic rocks in the eastern Lhasa Terrane, southern Tibet - Chenyuan Hua; Feng Huang; Song Zhang; Haiyan Fan; Yunchuan Zeng; Mingjian Li; Shuo Wang; Xi Chen; Jing Hu; Jifeng Xu (Lithos, 2025)

The spatial impact of population semi-urbanization on sulfur dioxide emissions: Empirical evidence from China - Zhenhua Zhang; Chao Hua; Xue-Li Chen; Malin Song (Journal of Environmental Management, 2025)

Lactiplantibacillus plantarum DACNJS22 alleviates benzo(a)pyrene-induced neurobehavioral injury in mice: Insights from gut microbiota and short-chain fatty acids - Yu-Hang Jiang; Yang-You Li; Wei-Gang Xin; Yu-Ting Zhao; Xiao-Yong Chen; Jia-Jia Song; Chen Wang; Hua-Yi Suo (Food Bioscience, 2025)

Optimized near infrared reflectance model based on preprocessing selection strategy for rapid analysis of 2-acetyl-1-pyrroline content in rice flour - Li-Hong Xie; Shao-Qing Tang; Gao-Neng Shao; Zhong-Hua Sheng; Shi-Kai Hu; Xiang-Jin Wei; Gui-Ai Jiao; Ling Wang; Pei-Song Hu (Food Control, 2025)

Simulation-assisted hapten screening for sensitive on-site and visual detection of diazinon pesticide in environmental water and food samples - Xiaoling Li; Aihong Wu; Maozhong Sun; Shanshan Song; Hua Kuang; Chuanlai Xu; Xiaoling Wu (Chemical Engineering Journal, 2025)

Light-emitting diodes affect plantlet growth of Spathiphyllum cannifolium by regulating photosynthesis and sucrose metabolism during ex vitro rooting - Shuo Yu; Kui-Hua Li; Hang-Lin Song; Yue Dai; Yin-Ji Jiang; Mei-Yu Jin; Xuan-Chun Piao; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Representing the Uncertainty of a 3D Geological Model via Global Optimum Truth Discovery Technology - Nan Li; Keyan Xiao; Shitao Yin; Cangbai Li; Xianglong Song; Wenkai Chu; Weihua Hua; Rui Cao (Natural Resources Research, 2025)

A rare tetrahydroimidazopyridine from the marine-derived fungus Paraconiothyrium sp. YK-03 - Wen-Ke Gao; Xiao-Yan Song; Shi-Wei Li; Bian-Xia Xue; Hong-Hua Wu; Li-Hua Zhang; Yue-Hu Pei (Natural Product Research, 2025)

Comparison of water quality, planktonic community, and volatile organic compounds in the seawater from five cage culture areas of large yellow croaker - Jia-Lang Zheng; Qing-Hao Zhan; Fa-Guo Wan; Yong-Long Chen; Tian-Hong Chen; Shang-Wei Xie; Li-Hua Jiang; Shun Chen; Qing-Ling Zhu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2025)

Dietary lecithin attenuates adverse effects of high fat diet on growth performance, lipid metabolism, endoplasmic reticulum stress and antioxidant capacity in the intestine of largemouth bass (Micropterus salmoides) - Hua Zheng; Biao Wang; Qing-Lin Li; Tao Zhao; Peng-Cheng Xu; Yu-Feng Song; Zhi Luo (Aquaculture, 2025)

Comparative analysis of carotenoids, fatty acids, minerals, tastes, and odor in the skin of wild versus farmed large yellow croaker: Superior nutritional benefits with elevated heavy metal risks - Jia-Lang Zheng; Tao Zhu; Wang-Yang Jin; Qing-Hao Zhan; Fa-Guo Wan; Yong-Long Chen; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Shuang Chen; Wei-Ye Li; Yi-Fan Liu; et al. (Aquaculture, 2025)

Conductive hydrogels with HPC additions for humidity sensing and temperature response - Lizhi Song; Wei‐Jing Chen; Jiarui Huang; Dinggen Hu; Xingxiang Ji; Li Hua; Zhaoqing Lu (Chemical Engineering Journal, 2025)

Simultaneously enhancing efficiency and thermo-/UV-stability of organic solar cells by regulating the nanomorphology of the polymer blend by an acrylated fullerene derivative - Haitao Song; Yaqian Dong; Zesheng Zhang; Jin Fang; Chao Yue; Yongzhen Yang; Chao Liu; Qing Guo; Hua Wang; Qun Luo; Wei-Shi Li; Lingpeng Yan; et al. (Chemical Engineering Journal, 2025)

Synergistic promotion of phenol hydrogenation by regulating specific surface area and oxygen vacancies based on the morphology dependent effect - Shuai Wang; Tairui Xue; Yuanyuan Wang; Xueqin Wang; Feng Li; Yanguang Chen; Yuxuan Tian; Bolong Jiang; Hua Song (Chemical Engineering Journal, 2025)

Progress in Transdifferentiation of Autologous Alternative Cell Sources into Corneal Epithelial Cells - Bei Wang; Jiang-Lan Zhao; Wan-Ying Cai; Gong-Yue Wang; Yu-Zhi Li; Jia-Song Wang; Hua-Tao Xie; Ming-Chang Zhang (Stem Cell Reviews and Reports, 2025)

Overexpression of OsSTP1 increases grain yield via enhancing carbohydrate metabolism and transport in rice - Dong Liu; Ming-juan Li; Jin-song Luo; Hai-fei Chen; Yong Yang; Gui Xiao; Jun Wu; Abdelbagi M. Ismail; Zhen-hua Zhang (Planta, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

The planting years of vineyards alters the carbon fixation pathways by soil autotrophic microorganism - Rui Song; Zongwen Zhu; Hua Li; Hua Wang (Agriculture, Ecosystems & Environment, 2025)

Effects of single or combined exposure to tralopyril and ocean acidification on energy metabolism response and sex development in Pacific oysters (Crassostrea gigas) - Ping Li; Minghao Yin; Xu Wang; Ruolan Jia; Chengzhaung Chen; Bin Liu; Yiwei Liu; Bianhao Zeng; Tengzhou Li; Ling Liu; Hong-Jun Song; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

Submerge-emerge alternation promotes sediment per- and polyfluoroalkyl substance (PFAS) release and bioaccumulation - Ye-bing Shi; Zu-lin Hua; Xiao-qing Li; Song-he Zhang; Jian-long Liu (Science of The Total Environment, 2024)

Probing fragile topology with dislocations - Ying Wu; Zhi-Kang Lin; Yating Yang; Zhida Song; Feng Li; Jian-Hua Jiang (Science Bulletin, 2024)

Effects of plasticizer on removal of antibiotics and antibiotic resistance genes from agricultural soils via soil microbial fuel cells - Huixiang WANG; Xiaoshuai SHEN; Chen ZHANG; Yi SHAO; Hua LI; Jian WU; Yuli YANG; Hailiang SONG (Pedosphere, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

AmTPS6 promotes trehalose biosynthesis to enhance the Cd tolerance in mangrove Avicennia marina - Ling-Yu Song; Jing Li; Lu-Dan Zhang; Zhao-Yu Guo; Chao-Qun Xu; Li-Wei Jiang; Jin-Yu Liu; Ji-Cheng Wang; Qing-Hua Li; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2024)

Myosin supramolecular self-assembly: The crucial precursor that manipulates the covalent aggregation, emulsification and rheological properties of myosin - Li Hu; Sinong Liu; Ruibang Zhang; Shuyi Song; Zhichao Xiao; Jun-Hua Shao (Food Research International, 2024)

The effect of pH shifting on the calcium-fortified milk analogue with chickpea protein - Junrong Liao; Zonglin Guo; Jiahai Shen; Xiaoqing Lin; Yuwei Wang; Wanqing Yuan; Christelle Turchiuli; Yuwei Li; Yijing Zhang; Jie Lin; Hua Zheng; Song Miao; et al. (Food Chemistry, 2024)

Microbial succession during spontaneous fermentation of Ecolly grapes and their important contribution to flavor metabolites - Yinting Ding; Lin Wang; Yujie Gao; Zhengwen Zhang; Yinghui Song; Hua Wang; Hua Li (Food Bioscience, 2024)

Sludge-derived biostimulants promote glycosylation of tricin and luteolin in the flavone and flavonol biosynthesis to enhance anti-inflammatory activities of rice - Xin Yuan; Yu Hua; Shu-xian Chen; Qi Song; Xiao-ou Li; Yue Zhang; Xiao-hu Dai (Environmental Research, 2024)

Optimization of sub-arc collimator angles in volumetric modulated arc therapy: a heatmap-based blocking index approach for multiple brain metastases - Shi-Xiong Huang; Song-Hua Yang; Biao Zeng; Xiao-Hua Li (Physical and Engineering Sciences in Medicine, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

Establishment of an immunoassay for detection of nonylphenols in surfactant oilfield chemicals based on computer-aided design - Jinyan Li; Yong Shu; Luming Jiang; Shanshan Song; Xinxin Xu; Xiaoling Wu; Hua Kuang; Chuanlai Xu; Lingling Guo (Science of The Total Environment, 2024)

Late Triassic basaltic andesites unveil inception of Neo-Tethys Ocean in Gyaca area of Tethyan Himalaya - Qinwen Gao; Feng Huang; Song Zhang; Yunchuan Zeng; Mingjian Li; Shuo Wang; Chenyuan Hua; Hongxia Yu; Yinhui Zhang; Jifeng Xu (Lithos, 2024)

Highly active metal–acid bifunctional B–doped radial channel silica supported Ni2P for efficient hydrodeoxygenation performance - Xiaomei Gou; Bolong Jiang; Tianhan Zhu; Qiang Zhang; Shuai Wang; Feng Li; Huan Wang; Hua Song (Fuel, 2024)

Enhancement of stress resistance of electroactive biofilms against hypersaline shock via exogenous electron mediator addition - Tao Li; Chen-ying Li; Han-lin Liang; Xiao-xue Li; Xiao-li Yang; Hua Li; Hai-liang Song (Chemical Engineering Journal, 2024)

Vineyard reclamation alters soil properties and microbial community in desertified land - Rui Song; Yongshan Li; Zongwen Zhu; Liang Zhang; Hua Wang; Hua Li (CATENA, 2024)

Zika virus infection induces glycometabolic disorder in northern pig-tailed macaques - Qing Li; Ren-Hua Yang; Yan Hu; Bei-Bei Tang; Ying-Jie Jiang; Chang-Bo Zheng; Tian-Zhang Song (Science China Life Sciences, 2024)

Link Brain-Wide Projectome to Neuronal Dynamics in the Mouse Brain - Xiang Li; Yun Du; Jiang-Feng Huang; Wen-Wei Li; Wei Song; Ruo-Nan Fan; Hua Zhou; Tao Jiang; Chang-Geng Lu; Zhuang Guan; Xiao-Fei Wang; Hui Gong; et al. (Neuroscience Bulletin, 2024)
Knowledge about the neuronal dynamics and the projectome are both essential for understanding how the neuronal network functions in concert. However, it remains challenging to obtain the neural activity and the brain-wide projectome for the same neurons, especially for neurons in subcortical brain regions. Here, by combining in vivo microscopy and high-definition fluorescence micro-optical sectioning tomography, we have developed strategies for mapping the brain-wide projectome of functionally relevant neurons in the somatosensory cortex, the dorsal hippocampus, and the substantia nigra pars compacta. More importantly, we also developed a strategy to achieve acquiring the neural dynamic and brain-wide projectome of the molecularly defined neuronal subtype. The strategies developed in this study solved the essential problem of linking brain-wide projectome to neuronal dynamics for neurons in subcortical structures and provided valuable approaches for understanding how the brain is functionally organized via intricate connectivity patterns.

Enhancing the nitrogen removal of anammox sludge by setting up novel redox mediators-mediated anammox process - Huahua Li; Hua Chen; Xinyuan He; Yi Lu; Haichun Gao; Hao Song; Shaoan Cheng (Chemosphere, 2024)

Comparative study on the quality of wild and ecologically farmed large yellow croaker through on-site synchronous sampling from the Nanji Archipelago in the East China Sea - Jia-Lang Zheng; Yong-Long Chen; Fa-Guo Wan; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Li-Hua Jiang; Wei-Ye Li; Wen-Tao Ye; Yi-Fan Liu; Wei-Hua Song; et al. (Aquaculture, 2024)

Preparation of umami peptides from chicken breast by batch coupled enzymatic hydrolysis and membrane separation mode and the taste mechanism of identified umami peptides - Jing Guo; Li Chen; Cunshan Zhou; Hafida Wahia; Deyang Yao; Linglin Song; Phyllis Otu; Ke Zhang; Yunwei Niu; Chenhui Hua (Food Chemistry, 2024)

Surface morphologic changes and mineral transformation mechanisms after CO2-brine-rock reaction in organic matter-rich ferroan shale - Xin Liu; Jingqiang Tan; Qixiang Wang; Hui Li; Guodong Han; Yonggang Ding; Xueqi Song; Ruobing Luo; Shihao Hua (Chemical Engineering Journal, 2024)

Multifunctional and immunoregulatory microenvironment-responsive hydrogel for whole course management of infected diabetic wounds - Zhenyu Luo; Xiaoxue Fu; Hua Jiang; Weikun Meng; Shue Jin; Yongrui Cai; Ze Du; Ping Song; Anjing Chen; Li Li; Peifang Li; Jiali Chen; et al. (Chemical Engineering Journal, 2024)

Spatiotemporal variation in rice evapotranspiration under the influence of rice expansion: a case study in the Sanjiang Plain, Northeast China - Yuqi Li; Xuhua Hu; Yufeng Luo; Yang Xu; Peng Huang; Dan Yuan; Changhong Song; Yuanlai Cui; Hua Xie (Paddy and Water Environment, 2024)

Multi-dimensional signals coupling of simultaneous acquisition stripping current with laser-induced breakdown spectroscopy for accurate analysis of Cd(II) in coexisting Cu(II) - Yuan-Fan Yang; Zong-Yin Song; Zi-Hao Liu; Zhi-Wei Gao; Xin Cai; Cong-Cong Huang; Pang-Da Dai; Meng Yang; Pei-Hua Li; Shi-Hua Chen; Xing-Jiu Huang (Analytica Chimica Acta, 2024)

Enhancing CO2 storage and marine carbon sink based on seawater mineral carbonation - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Shuo Chen Li; Zhi Bo Wang; Jun Ma (Marine Pollution Bulletin, 2024)

Comparative study on the morphological characteristics, nutritional quality, and tastes of large yellow croaker from five cage culture areas: Relay farming improved fish quality - Jia-Lang Zheng; Fa-Guo Wan; Yong-Long Chen; Li-Hua Jiang; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Lin Zhu; Wei-Ye Li; Yi-Fan Liu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2024)

Characteristics analysis of leakage diseases of Beijing underground subway stations based on the field investigation and data statistics - Hua Peng; Yujie Li; Xiaokai Niu; Haidong Tang; Xue Meng; Zichen Li; Kuangdi Wan; Wei Li; Wei Song (Transportation Geotechnics, 2024)

Insights to the cooperation of double-working potential electroactive biofilm for performance of sulfamethoxazole removal: ARG fate and microorganism communities - Tao Li; Chen-Ying Li; Yan-Fei Wang; Jing-Nan Zhang; Hua Li; Hui-Fang Wu; Xiao-Li Yang; Hai-Liang Song (Journal of Hazardous Materials, 2024)

Foliar-selenium enhances plant growth and arsenic accumulation in As-hyperaccumulator Pteris vittata: Critical roles of GSH-GSSG cycle and arsenite antiporters PvACR3 - Wei Li; Si-Xue He; Qian-Yu Zhou; Zhi-Hua Dai; Chen-Jing Liu; Shu-Fen Xiao; Song-Ge Deng; Lena Q. Ma (Journal of Hazardous Materials, 2024)

Human activities-impacted lake dissolved organic matter (DOM) affects phycosphere microbial diversity and DOM diversification via carbon metabolism - Yingyue Song; Xinghong Cao; Sheng-Ao Li; Zhe Li; Hans-Peter Grossart; Hua Ma (Journal of Environmental Management, 2024)

Properties, extraction and purification technologies of Stevia rebaudiana steviol glycosides: A review - Chengxia Huang; Yang Wang; Cunshan Zhou; Xingyu Fan; Qiaolan Sun; Jingyi Han; Chenhui Hua; Yao Li; Yunwei Niu; Clinton Emeka Okonkwo; Deyang Yao; Linglin Song; et al. (Food Chemistry, 2024)

Full-field straw mulching and fertilizer application improved the soybean seed yield through optimization of the root and canopy structure: A study case in Huang-Huai-Hai region - Zongsheng Wu; Cailong Xu; Ruidong Li; Yifan Xu; Jianxin Hua; Shi Sun; Tianfu Han; Wenwen Song; Cunxiang Wu (European Journal of Agronomy, 2024)

Protective layer constructed by liquid phase quenching for long lifespan potassium ion batteries - Shedong Li; Lu-Kang Zhao; Yu-Hua Bian; Hong Chen; Xuan-Wen Gao; Yingying Song; Zhaomeng Liu; Wen-Bin Luo (Chemical Engineering Journal, 2024)

A novel anti-angiogenesis peptide in combination with cisplatin self-assembling into tube-like nanomedicine for oral treatment of gastric cancer - Linwei Chen; Qin Wang; Yong Jiang; Liu Xu; Nina Wei; Chang Lu; Chenqi Chang; Dandan Song; Yutong Wang; Li Wu; Weidong Li; Xiaobin Jia; et al. (Chemical Engineering Journal, 2024)

Enhanced Hydrodeoxygenation performance through novel Al-Doped radial channel Silica-Supported Carbon-Encapsulated nickel catalysts - Bolong Jiang; Yuhan Zhang; Huan Wang; Kun Liu; Nan Jiang; Jiayou Li; Hua Song; Yanguang Chen (Chemical Engineering Journal, 2024)

Green production of airport terminals considering carbon footprint and indoor air quality: A multi-objective optimization perspective - Sheng-Hua Xiong; Xin Xiong; Gang Li; Witold Pedrycz; Muhammet Deveci; Zhen-Song Chen (Building and Environment, 2024)

Mutations in wheat TaAPA2 gene result in pleiotropic effects on plant architecture - Shengsheng Bai; Guiping Wang; Rui Song; Yanna Liu; Lei Hua; Jinwei Yang; Lijun Zhang; Shams ur Rehman; Xiaohua Hao; Lifeng Hou; Chaozhong Zhang; Hongna Li; et al. (Science China Life Sciences, 2024)

Fungicides reduce soil microbial diversity, network stability and complexity in wheat fields with different disease resistance - Lei Zhang; Qinglin Zuo; Hua Cai; Shuo Li; Zhen Shen; Ting Song (Applied Soil Ecology, 2024)

Establishment of a callus induction system of Saxifraga stolonifera Meerb. and its response to different elicitors - Lin Song; Ta Zhao; Chun-Li Luo; Jin-Ling Li; Song-Shu Chen; Dan-Dan Li; Jin Liang; Hong-Chang Liu; Fu-Lai Luo; Ming-Jin Huang; Hua-Lei Wang (South African Journal of Botany, 2024)

Health risks and sources of trace elements and black carbon in PM2.5 from 2019 to 2021 in Beijing - Chenjie Hua; Wei Ma; Feixue Zheng; Yusheng Zhang; Jiali Xie; Li Ma; Boying Song; Chao Yan; Hongyan Li; Zhen Liu; Qian Liu; Markku Kulmala; et al. (Journal of Environmental Sciences, 2024)

New simple method for calculating large-strain consolidation settlement of layered soft soils with horizontal drains and vacuum preloading with comparison to test data - Ze-jian Chen; Peng-lin Li; An Li; Jian-hua Yin; Ding-bao Song (Geotextiles and Geomembranes, 2024)

Ameliorating the electronic environment of NiCoP by halogen doping: A strategy for boosting hydrogen evolution performance - Jian Su; Nan Jiang; Bolong Jiang; Yuanyuan Wang; Xueqin Wang; Zhijun Li; Hua Song (Fuel, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Synergistic doping and de-doping of Co3O4 catalyst for effortless formaldehyde oxidation - Wenhao Meng; Xuedan Song; Liurui Bao; Bingbing Chen; Zhen Ma; Jing Zhou; Qike Jiang; Fanyu Wang; Xiao Liu; Chuan Shi; Xingyun Li; Hua Zhang (Chemical Engineering Journal, 2024)

Cell-Free DNA in Plasma Reveals Genomic Similarity Between Biliary Tract Inflammatory Lesion and Biliary Tract Cancer - Ruimei Liu; Yueqiang Song; Rulin Hua; Shariq Ahmed; Yunxiao Xie; Cong Lai; Jialu Xu; Fuyuan Li; Ying Li; Zhiguang Li; Yinping Wang; Dekang Lv; et al. (Phenomics, 2024)

Identification of the Galactinol Synthase (GolS) Family in Medicago truncatula and Expression Analysis Under Abiotic Stress and Phytohormone Treatment - Hua Li; Ying Di Gao; Li Qing Kang; Hong Yang Yu; Li Ming Zeng; Yi Hua Wang; Rong Rong Chen; Jian Bo Song (Journal of Plant Growth Regulation, 2024)

Multiple Matching Attenuation Based on Curvelet Domain Extended Filtering - Qingfeng Hua; Zhang Chen; Huili He; Jun Tan; Haifeng Chen; Guanbao Li; Peng Song; Bo Zhao; Xiuping Jiang (Journal of Ocean University of China, 2024)

Caspase-12 is Expressed in Purkinje Neurons and Prevents Psychiatric-Like Behavior in Mice - Lin-Yan Huang; Yi-Ning Liu; Jie Chen; Hai-Xue Zhu; Li-Li Li; Zhi-Yan Liang; Jin-Xiu Song; Yu-Jie Li; Zhao-Li Hu; Dieter Demon; Andy Wullaert; Wan Wang; et al. (Molecular Neurobiology, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Anaerobic cyanides oxidation with bimetallic modulation of biological toxicity and activity for nitrite reduction - Acong Chen; Haoling Li; Haizhen Wu; Zhaohui Song; Yao Chen; Heng Zhang; Zijun Pang; Zhi Qin; Yulun Wu; Xianghong Guan; Hua Huang; Zemin Li; et al. (Journal of Hazardous Materials, 2024)

Elucidation of the beneficial role of co-fermented whole grain quinoa and black barley with Lactobacillus on rats fed a western-style diet via a multi-omics approach - Zi-Han Lin; Ling-Yue Zhong; Hui-Bin Jiang; Chuang Zhu; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Research International, 2024)

Rapid and sensitive quantitation of amitraz in orange, tomato, and eggplant samples using immunochromatographic assay - Qianqian Lu; Liqiang Liu; Jinyan Li; Shanshan Song; Hua Kuang; Chuanlai Xu; Lingling Guo (Food Chemistry, 2024)

Versatile MOF-based nanofibrous heterostructures for engineering the CO2 photoreduction activity and selectivity: From CO to C2H5OH - Xu-Chao Xia; Feng Cheng; Peng Sun; Amare Aregahegn Dubale; Hao Han; En-Tian Cui; Jun Song; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2024)

Reverse loading of inert Al2O3 onto active iron oxide for improved H2O2 activation and pollutant degradation - Chunli Song; Tian Xu; Jiuhe Bu; Hongchao Li; Xuan Zhang; Xiaodong Wang; Yuanqing Bu; Ming Hua; Bingcai Pan; Jieshu Qian (Chemical Engineering Journal, 2024)

Rice rhizospheric effects and mechanism on soil cadmium bioavailability during silicon application - Yi Yang; Hua Peng; Kai Deng; Yu Shi; Wei Wei; Saihua Liu; Changjun Li; Jian Zhu; Yanjiao Dai; Min Song; Xionghui Ji (Science of The Total Environment, 2024)

Post-glacial small delta process uncovered by luminescence and radiocarbon chronology of core sediments from coastal South China Sea - Yuexin Liu; Guanjun Xu; Gui Long; Yingjin Song; Ruonan Tian; Yanwen Li; Hua Tu; Hongwei Li; Zhongping Lai (Quaternary Geochronology, 2024)

Axisymmetric finite strain consolidation model for soft soil consolidation with vertical drains under combined loading considering creep and non-Darcy flow - Peng-Lin Li; Zhen-Yu Yin; Ding-Bao Song; Jian-Hua Yin; Yu Pan (Geotextiles and Geomembranes, 2024)

Revealing the interaction forms between Hg(II) and group types (–Cl, –CN, –NH2, –OH, –COOH) in functionalized Poly(pyrrole methane)s for efficient mercury removal - Zhenyu Wang; Aijing Zhang; Tingyu Hua; Xin Chen; Mengyuan Zhu; Ziyu Guo; Yanna Song; Guorui Yang; Shanshan Li; Jiangtao Feng; Mingtao Li; Wei Yan (Environmental Pollution, 2024)

Characterization of the complete mitochondrial genome of Ergasilus anchoratus Markevich, 1946 (Ergasilidae) and phylogeny of Copepoda - Cong-jie Hua; Yan Huang; Hui-quan Li; Jin-mei Feng; Jia-lu Qiao; Song Hu; Wei Liu; Xi-ji Shu (Systematic Parasitology, 2024)

In-situ precipitation zero-valent Co on Co2VO4 to activate oxygen vacancies and enhance bimetallic ions redox for efficient detection toward Hg(II) - Zhi-Wei Gao; Hao Li; Pei-Hua Li; Yong-Yu Li; Jia-Qing Quan; Na Ma; Shi-Hua Chen; Xing-Jiu Huang; Zong-Yin Song; Meng Yang (Analytica Chimica Acta, 2024)

Significance of neutrophil extracellular traps-related gene in the diagnosis and classification of atherosclerosis - Liantai Song; Boyu Zhang; Reng Li; Yibing Duan; Yifan Chi; Yangyi Xu; Xucong Hua; Qian Xu (Apoptosis, 2024)

Two new degrade triterpenoids from Buxus bodinieri Levl. - Yu-Xin Yan; Na-Li Song; Ji-Hong Zhang; Ming-Hua Qiu (Natural Product Research, 2024)

Airborne ARGs/MGEs from two sewage types during the COVID-21: Population, microbe interactions, cytotoxicity, formation mechanism, and dispersion - Yanjie Wang; Song Zhang; Lin Li; Qiao Zhang; Liying Yang; Kai Yang; Yang Liu; Haoran Zhu; Bisheng Lai; Jian Wu; Linlin Hua (Water Research, 2024)

BDNF mimetics recover palmitic acid-induced injury in cardiomyocytes by ameliorating Akt-dependent mitochondrial impairments - Man-Ru Zhang; Bang-Yun Zuo; Yu-Chen Song; Dan-Dan Guo; Qing-Liu Li; Jin-Xiu Lyu; Hua Zhu; Jing Zhao; Peng-Zhou Hang (Toxicology and Applied Pharmacology, 2024)

Spatiotemporal distribution, interactions and toxic effect of microorganisms and ARGs/MGEs from the bioreaction tank in hospital sewage treatment facility - Yanjie Wang; Song Zhang; Liying Yang; Kai Yang; Yang Liu; Haoran Zhu; Bisheng Lai; Lin Li; Linlin Hua (Science of The Total Environment, 2024)

Photochemical processes transform dissolved organic matter differently depending on its initial composition - Sheng-Ao Li; Qianru Wang; Hua Ma; Xinghong Cao; Yingyue Song; Fuyi Cui; Andrew J. Tanentzap (Science of The Total Environment, 2024)

Non-additive effect: Variation in the effects of the interaction between primitive components in anaerobic digestion - Yu Hua; Qi Song; Liyin Li; Shuxian Chen; Boran Wu; Xiaohu Dai (Resources, Conservation and Recycling, 2024)

Quantitative immunochromatographic assay for rapid and cost-effective on-site detection of benzo[a]pyrene in oilfield chemicals - Jinyan Li; Luming Jiang; Yong Shu; Shanshan Song; Liguang Xu; Hua Kuang; Chuanlai Xu; Lingling Guo (Journal of Hazardous Materials, 2024)

Change characteristics, bacteria host, and spread risks of bioaerosol ARGs/MGEs from different stages in sewage and sludge treatment process - Yanjie Wang; Kai Yang; Lin Li; Liying Yang; Song Zhang; Fangfang Yu; Linlin Hua (Journal of Hazardous Materials, 2024)

Transoceanic ships as a source of alien dinoflagellate invasions of inland freshwater ecosystems - Lixia Shang; Zhangxi Hu; Yunyan Deng; Jing Li; Yuyang Liu; Xiaoying Song; Xinyu Zhai; Zifeng Zhan; Wen Tian; Jinxiang Xu; Yangchun Han; Hao Shen; et al. (Harmful Algae, 2024)

Condition monitoring for bridge cables using time-history area of cable forces under stochastic traffic flow - De-Long Li; Dong-Hui Yang; Ting-Hua Yi; Song-Han Zhang; Hong-Nan Li (Engineering Structures, 2024)

Outsourcing carbon emissions of the expanding affluent groups in China - Liyuan Wei; Xuan Jiang; Hua Yan; Manfred Lenzen; Mengyu Li; Arunima Malik; Vivienne Reiner; Zhen Wang; Song Hong (Environmental Impact Assessment Review, 2024)

Inhibiting platinum sintering in direct ethane dehydrogenation and nonoxidative methane activation reactions by sequential sulfide layered chemical vapor deposition - Jack S. Jarvis; Zhaofei Li; Zhiqiang Wang; Lijia Liu; Lo-Yueh Chang; Avinash Alagumalai; Hua Song (Chemical Engineering Journal, 2024)

Development of a multi-layer network model for characterizing energy cascade behavior on turbulent mixing - Beibei Mao; Hua Yang; Dalei Song; Junyang Li; Weicheng Sun; Xiuyan Liu (Frontiers in Marine Science, 2024)
Eddies of various sizes are visible to the naked eye in turbulent flow. Each eddy scale corresponds to a fraction of the total energy released by the turbulence cascade. Understanding the dynamic mechanism of the energy cascade is crucial to the study of turbulent mixing. In this paper, an energy cascade multi-layer network (ECMN) based on the complex network algorithm is proposed to investigate the spatio-temporal evolution of the energy cascade, covering both the inertial and dispersive ranges. The dynamic process of energy cascade is transformed into a topological structure based on the node definition and edge determination. The topological structure allows for the exploration of eddies interaction and chaotic energy transfer across scales. The model results show the intermittent and non-uniform nature of the energy cascade. Meanwhile, the scale gap found in the model verifies the fractal property of the energy evolution. We also found that scales of the generated eddies in energy cascade process are stochastic, and a synchronous energy cascade pattern is demonstrated according to the constructed framework. Furthermore, it provides a topological way to evaluate the contribution of large and small scale eddies. In addition, a network structure coefficient κ is proposed to evaluate the energy transfer strength. It agrees very well with the fluctuation of dissipation rates. All of this shows that the network model can effectively reveal the inhomogeneous properties of the energy cascade and quantify the turbulent mixing intensity based on the intermittent scale interaction. This also provides new insights into the study of fractal scales of nonlinear complex systems and the bridging of chaotic dynamics with topological frameworks.

Boron-mediated amelioration of copper toxicity in Citrus sinensis seedlings involved reduced concentrations of copper in leaves and roots and their cell walls rather than increased copper fractions in their cell walls - Huan-Huan Chen; Zhi-Chao Zheng; Dan Hua; Xu-Feng Chen; Zeng-Rong Huang; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2024)

The polyphenols profile of co-fermented quinoa and black barley with Lactobacillus kisonensis and its in vitro bioactivities - Hui-Bin Jiang; Pan Nie; Zi-Han Lin; Chuang Zhu; Ling-Yue Zhong; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Bioscience, 2024)

CRISPR/Cas9-mediated knockout of Bsr-d1 enhances the blast resistance of rice in Northeast China - Ying Zhang; Xiu-Feng Lin; Li Li; Ri-Hua Piao; Songquan Wu; Anqi Song; Mengmeng Gao; Yong-Mei Jin (Plant Cell Reports, 2024)

Examination of the effects of triacylglycerol lipase on astaxanthin conversion in the black tiger prawn Penaeus monodon - Xin-Tao Li; Li-Shi Yang; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Fa-Lin Zhou; Yun-Dong Li; Jian-Zhi Shi; Xu Chen; Yu-kai Yang; Jian-Hua Huang (Aquaculture, 2024)

Mechanisms of LPS–induced epithelial mesenchymal transition in bEECs - Mingkun Sun; Pengjie Song; Yu Zhao; Bowen Li; Ping Wang; Zhipeng Cong; Song Hua (Theriogenology, 2024)

Iron oxide nanoclusters formed by acid-induced in situ calcium ion cross-linking for targeted magnetic resonance imaging of glioblastoma - Ruoxi Xie; Shengxiang Fu; Guannan Zhu; Hua Ai; Bin Song; Su Lui; Gaocan Li; Yunbing Wang; Min Wu (Chemical Engineering Journal, 2024)

Correction to: Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2024)

Enhanced indigenous consortia for the remediation of uranium-contaminated groundwater by bioaugmentation: Reducing and phosphate-solubilizing consortia - Guo-hua Wang; Jian Song; Zhi-yue Zhang; Quan-jin Xiao; Shan He; Tao-tao Zeng; Ying-jiu Liu; Shi-you Li (Science of The Total Environment, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Synergistic activation of P and orbital coupling effect for ultra-sensitive and selective electrochemical detection of Cd(II) over Fe-doped CoP - Zhi-Wei Gao; Yong-Yu Li; Pei-Hua Li; Yuan-Fan Yang; Yong-Huan Zhao; Meng Yang; Shi-Hua Chen; Zong-Yin Song; Xing-Jiu Huang (Journal of Hazardous Materials, 2024)

In-situ sodium chloride template synthesis of γ-WO3 hollow cubes for high-sensing and dual-selective hydrazine/dibutylamine detection at different temperatures - Guo-Li Chen; Ming-Song Lv; Jing Zhang; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

High-density lipoprotein regulates angiogenesis by affecting autophagy via miRNA-181a-5p - Bi-Ang Kang; Hua-Ming Li; Ya-Ting Chen; Meng-Jie Deng; Yan Li; Yue-Ming Peng; Jian-Jun Gao; Zhi-Wei Mo; Jia-Guo Zhou; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2024)

An Uncertainty Analysis Method Based on a Globally Optimal Truth Discovery Model for Mineral Prospectivity Mapping - Nan Li; Shitao Yin; Cangbai Li; Yishi Wang; Keyan Xiao; Rui Cao; Weihua Hua; Wenkai Chu; Xianglong Song; Cheng Li (Mathematical Geosciences, 2024)

Phosphorus-doped synergy of phase change in heterogeneous catalysts of NiS–NiS2 for efficient electrocatalysis of Pb(II) - Yong-Yu Li; Kai-Yuan Li; Shi-Hua Chen; Na Ma; Zong-Yin Song; Meng Yang; Jie Wang; Wen-Qing Liu (Analytica Chimica Acta, 2024)

Composite vertical structures and spatiotemporal characteristics of abnormal eddies in the Japan/East Sea: a synergistic investigation using satellite altimetry and Argo profiles - Yaowei Ma; Qinghong Li; Hua Wang; Xiangjun Yu; Song Li (Frontiers in Marine Science, 2024)
Mesoscale eddies are omnipresent and play an important role in regulating Earth’s climate and ocean circulation in the global ocean. Here using the combination of satellite altimetry products and Argo float profile data, two types of abnormal eddies are investigated: WCEs(warm cyclonic eddies) and CAEs(cold anticyclonic eddies) with different cores than conventional eddies in the Japan/East Sea. By applying a classification method based on the calculation of the heat content anomalies in the upper ocean, it was found that 10% of the eddies that captured the Argo float profiles exhibited obvious abnormal features. Subsequently, their spatiotemporal distributions and characteristics were analyzed statistically. Three-dimensional structures of abnormal eddies were obtained via the composite analysis method, showing that the warm/cold and light/dense core of the composite WCE/CAE is confined to the upper 100 m of the ocean with a maximum temperature anomaly of approximately +1.0(-1.1)° C . The composite WCE had a double-core salinity structure with a salty core above 50 m and an inferior fresh core. Meanwhile composite CAE had a fresh single-core with a maximum magnitude of -0.05 psu. Abnormal eddies are pervasive in the Japan/East sea, a revaluation of the role of these eddies in ocean circulation and climate systems, such as heat and salt transport, air and sea interaction, and variability in mixed layer depth, is of great importance.

Sesquiterpenoids from aged Artemisia argyi and their 3D-QSAR for anti-HBV activity - Yu-Ying Song; Yong-Zhi Zhou; Yun-Fen Wang; Teng-Yun Shu; Yang Feng; Min Xu; Li-Hua Su; Hai-Zhou Li (Phytochemistry, 2024)

Characterizing accumulation and negative effects of aerosol particles on the leaves of urban trees - Siqi Chen; Hua Yu; Liang Xu; Fangmin Fei; Yaobin Song; Ming Dong; Weijun Li (Environmental Pollution, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Soil pH differently affects N2O emissions from soils amended with chemical fertilizer and manure by modifying nitrification and denitrification in wheat-maize rotation system - Gong Wu; Fei Liang; Qi Wu; Xiao-Gang Feng; Wen-ding Shang; Hua-wei Li; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Biology and Fertility of Soils, 2024)

Moraxella haemolytica sp. nov., isolated from a goat with respiratory disease - Fu-Xiang Li; Wen-Hua Zhao; Zhan-Hong Li; Jian-Ling Song; Hua-Feng Gao (Archives of Microbiology, 2024)

Staphylococcus warneri strain XSB102 exacerbates psoriasis and promotes keratinocyte proliferation in imiquimod-induced psoriasis-like dermatitis mice - Wenhao Si; Min Li; Kuan Wang; Jialin Li; Mengke Xu; Xiaoyue Zhou; Jie Bai; Zhiyuan Qu; Guoyan Song; Xueya Wu; Yuqi Guo; Hua Hu; et al. (Archives of Microbiology, 2024)

Investigation of the acicular aragonite growth behavior in AOD stainless steel slag during slurry-phase carbonation - Ya-Jun Wang; Jun-Guo Li; Meng-Jie Tao; Xi Zhang; Jian-Bao Zhang; Song Qin; Shao-Hua Liu; Li-Jie Peng; Xiao-Pei Zhang; Ya-Nan Zeng (Science of The Total Environment, 2023)

Background noise model of spaceborne photon-counting lidars over oceans and aerosol optical depth retrieval from ICESat-2 noise data - Jian Yang; Huiying Zheng; Yue Ma; Pufan Zhao; Hui Zhou; Song Li; Xiao Hua Wang (Remote Sensing of Environment, 2023)

Effects of NH+4 concentration on the vaterite formation via direct carbonation use waste carbide slag under the different ammonium systems - Xuewen Song; Yuxin Tuo; Ying Liang; Ziwei Tang; Mingfei Li; Xinrui Hua; Renhe Yang; Xianzhong Bu; Xianping Luo (Journal of Environmental Chemical Engineering, 2023)

Recent progress of the transition metal-based catalysts in the catalytic biomass gasification: A mini-review - Shijun Meng; Wenping Li; Zhaofei Li; Hua Song (Fuel, 2023)

Effects of Mixed Cropping on Sugarcane Growth and the Community of Arbuscular Mycorrhizal Fungi - Ying-Jie Nong; Qian Wang; Juan Song; Jin-Lian Zhang; Xiao-Juan Qin; Yi-Hao Kang; Xiang-Hua Wei; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2023)

Shoot Production of Solanum tuberosum L. ‘Yansi’ Using a Simple Continuous Immersion Airlift Bioreactor Culture System - Hang-Lin Song; Rong-de Jin; Xue-Li Quan; Ji-De Zhang; Wen-Wen Qi; Xi-Hua Cui (Potato Research, 2023)

Subsurface sound channel and seasonal variation of its characteristics in the mid-latitude of Northwest Pacific - Gengming Zhang; Lei Zhang; Yitao Wang; Hua Wang; Song Li; Weishuai Xu; Yue Yu; Yinfei Zhou; Qinghong Li; Xiangjun Yu; Xiaofang Sun (Journal of Oceanography, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Complete genome sequence of Paris polyphylla chlorotic mottle virus infecting Paris polyphylla var. yunnanensis in southwest China - Qiongji He; Binghua Chen; Hongying Zheng; Yuhao Cao; Mengyin Hua; Yueyan Yin; Jiejun Peng; Junmin Li; Jianping Chen; Fei Yan; Xuemei Song; Lin Lin (Archives of Virology, 2023)

Heterogeneous oxidative desulfurization of fuels using amphiphilic mesoporous phosphomolybdate-based poly(ionic liquid) over a wide temperature range - Shao-Xu Mao; Jun-Yi Song; Wen-Shuai Zhu; Hua-Ming Li; Jing-Yu Pang; Dong-Bin Dang; Yan Bai (Fuel, 2023)

Methane-assisted selective bio-oil deoxygenation for high-quality renewable fuel production: A rational catalyst design and mechanistic study - Jack Jarvis; Hao Xu; Yimeng Li; Zhaofei Li; Wenping Li; Shijun Meng; Lo-Yueh Chang; Lijia Liu; Hua Song (Chemical Engineering Journal, 2023)

Test of the colonization ability of the invasive alien plant Flaveria bidentis (Asteraceae) in southern China - Li Xin-Chen; Chen Xi; Dong Xue-jing; Wang Lai-Le; Yi-chen Li; Shi Zhi-Hua; Song Xiao-ling; Qiang Sheng; Dai Wei-min; Wei-Min Dai (Biological Invasions, 2023)

Natural and sustainable wine: a review - Ruteng Wei; Lin Wang; Yinting Ding; Liang Zhang; Feifei Gao; Ning Chen; Yinghui Song; Hua Li; Hua Wang (Critical Reviews in Food Science and Nutrition, 2023)

Enhanced removal of antibiotic and antibiotic resistance genes by coupling biofilm electrode reactor and manganese ore substrate up-flow microbial fuel cell constructed wetland system - Hua Li; Kun Wang; Jiale Xu; Huifang Wu; YuanJiXiang Ma; Rusen Zou; Hai-Liang Song (Chemosphere, 2023)

Detecting endosperm cracks in soaked maize using μCT technology and R-YOLOv7-tiny - Yitao Jiao; Zheng Wang; Yuying Shang; Rong Li; Zhixin Hua; Huaibo Song (Computers and Electronics in Agriculture, 2023)

Recent positive selection signatures reveal phenotypic evolution in the Han Chinese population - Huaxia Luo; Peng Zhang; Wanyu Zhang; Yu Zheng; Di Hao; Yirong Shi; Yiwei Niu; Tingrui Song; Yanyan Li; Shilei Zhao; Hua Chen; Tao Xu; et al. (Science Bulletin, 2023)

PANI grafted onto waste poros polyurethane for co-adsorption of multiple pollutants in industrial wastewater - Ning Wang; Yirui Guo; Yi Song; Wei Yan; Xuesong Gong; Yunfeng Li; Rui hua Mu; Yonghong Liu; Luohong Zhang (Journal of Water Process Engineering, 2023)

Copper enhanced arsenic-accumulation in As-hyperaccumulator Pteris vittata by upregulating its gene expression for As uptake, translocation, and sequestration - Chen-Jing Liu; You-Jing Peng; Chun-Yan Hu; Si-Xue He; Shu-Fen Xiao; Wei Li; Song-Ge Deng; Zhi-Hua Dai; Lena Q. Ma (Journal of Hazardous Materials, 2023)

Biofilm electrode reactor coupled manganese ore substrate up-flow microbial fuel cell-constructed wetland system: High removal efficiencies of antibiotic, zinc (II), and the corresponding antibiotic resistance genes - Hua Li; Haipeng Cao; Tao Li; Zhiming He; Jinhui Zhao; Yifeng Zhang; Hai-Liang Song (Journal of Hazardous Materials, 2023)

Fate of Cd during mineral transformation by sulfate-reducing bacteria in clay-size fractions from soils with high geochemical background - Xing Yan; Dong-Xing Guan; Jie Li; Yinxian Song; Hua Tao; Xianming Zhang; Ming Ma; Junfeng Ji; Wancang Zhao (Journal of Hazardous Materials, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Temperature-dependent NO2/diisopropylamine sensor based on SnO2 squama-wrapped tubes derived from waste bamboo shoot skin - Bao-Yu Song; Cong Chen; Ya-Nan Li; Xian-Fa Zhang; Xiao-Li Cheng; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

A Multifractal Cascade Model for Energy Evolution and Dissipation in Ocean Turbulence - Xiuyan Liu; Yufei Zhang; Dalei Song; Hua Yang; Xinyu Li (Journal of Marine Science and Engineering, 2023)
Scale properties and energy dissipation in the turbulent energy transfer process play an important role in deeply understanding the features of ocean turbulence. In this paper, a universal multifractal cascade model is applied to investigate scale and intermittency properties of a turbulent flow, and two sets of measured turbulence datasets in horizontal and vertical directions are performed for comprehensive experimental verification. First, an empirical mode decomposition method is utilized to adaptively decompose microstructure shear time series into several intrinsic mode functions. Then, the multifractal spectrum is calculated to extract multifractal features for different time scales. The ocean microstructure field shows an asymmetric structure with a left truncation and a long right tail in different directions. This proves that most energy transfer processes occur on small scales. Finally, the calculated multifractal indexes of all intrinsic mode functions for two datasets show that the intermittency of turbulence decreases with the increase in time scales, which reflects the multifractal intensity and the level of intermittency of turbulence. The multifractal cascade model can successfully build a bridge between intermittency and dissipation in the multiscale energy cascade process.

Silica mitigated calcium mineral scaling in brackish water reverse osmosis - Kai-Ge Lu; Shuanglong Ma; Dangling Hua; Hongen Liu; Chang Li; Jia Song; Haiou Huang; Yuchen Qin (Water Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Selective degradation of antibiotic in a novel Cu7S4/peroxydisulfate system via heterogeneous Cu(III) formation: Performance, mechanism and toxicity evaluation - Xieping He; Yining Lu; Tao Cai; Xijun Fu; Lu Song; Minjie Wang; Qingyi Zeng; Qingming Zeng; Mi Li; Yilong Hua; Xiaoyan Wu; Longlu Wang (Journal of Hazardous Materials, 2023)

Soybean lecithin and cholesterol-loaded cyclodextrin in combination to enhances the cryosurvival of dairy goat semen - Rong Li; Hubei Zhao; Bowen Li; Siqi Wang; Song Hua (Cryobiology, 2023)

Non-thermal plasma assisted catalytic nitrogen fixation with methane at ambient conditions - Hoang M. Nguyen; Ali Omidkar; Wenping Li; Shijun Meng; Zhaofei Li; Hua Song (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

Anti-apoptotic effect of adrenomedullin gene delivery on Leydig cells by suppressing TGF-β1 via the Hippo signaling pathway - You-wen Luo; Xia-lian Zhu; Ming-yong Li; Jian-hua Zhou; Zhi-min Yang; Tao Tong; Bing-hai Chen; Song-lin Qin; Bo-long Liu; Wei Hu (Reproductive Toxicology, 2023)

Techno-economic and life cycle assessment of renewable diesel production via methane-assisted catalytic waste cooking oil upgrading - Ali Omidkar; Hao Xu; Zhaofei Li; Kamran Haddadian; Hua Song (Journal of Cleaner Production, 2023)

First transcriptome profiling in gill and hepatopancrease tissues of Metapenaeus ensis in response to acute ammonia-N stress - Yun-Dong Li; Meng-Ru Si; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Li-Shi Yang; Jian-Hua Huang; Fa-Lin Zhou (Fish & Shellfish Immunology, 2023)

Anomaly diagnosis of stay cables based on vehicle-induced cable force sums - De-Long Li; Dong-Hui Yang; Ting-Hua Yi; Song-Han Zhang; Wen-Jie Li; Chong Li (Engineering Structures, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

TMEM151A variants associated with paroxysmal kinesigenic dyskinesia - Hua lin Huang; Qing xia Zhang; Fei Huang; Xiao yan Long; Zhi Song; Bo Xiao; Guo liang Li; Cai yu Ma; Ding Liu (Human Genetics, 2023)

Santalane-type sesquiterpenoids and isobenzofuranones from cultures of Paraconiothyrium sporulosum YK-03 - Li-Hua Zhang; Wen-Ke Gao; Shi-Wei Li; Xiao-Yan Song; Hong-Hua Wu; Hai-Feng Wang; Gang Chen; Shao-Xia Wang; Yue-Hu Pei (Phytochemistry, 2023)

Stimulator of interferon genes from Asian swamp eel (MaSTING) is involved in host defense against bacterial infection - Fei Meng; Rongrong Liu; Meijiao Song; Jiayue Wei; Hua Li; Liguo An; Guiwen Yang; Shijuan Shan (Fish & Shellfish Immunology, 2023)

Src inhibition induces mitotic arrest associated with chromosomal passenger complex - Song Yang; Youguang Luo; Mulin Yang; Hua Ni; Hanxiao Yin; Ming Hu; Min Liu; Jun Zhou; Yunfan Yang; Dengwen Li (Cell and Tissue Research, 2023)

Chinese version of the auditory verbal learning test: normative study and clinical applications in Chinese-speaking population in Shijiazhuang city - Fang-Ming Dong; Wei Wang; Shang-Zun Guo; Kai Shao; Ya-Xue Song; Ning Han; Yan-Li Jia; Rong-Fang Feng; Jian-Hua Wang (Acta Neurologica Belgica, 2023)

Pentacyclic triterpenoids from spikes of Prunella vulgaris L. with thyroid tumour cell cytostatic bioactivities - Xiu-Qin Zheng; Lei-Xin Song; Zhu-Zhen Han; Ying-Bo Yang; Yi Zhang; Li-Hua Gu; Li Yang; Gui-Xin Chou; Zheng-Tao Wang (Natural Product Research, 2023)

Comprehensive phylogenomic analyses reveal that order Armophorida is most closely related to class Armophorea (Protista, Ciliophora) - Jia Li; Song Li; Hua Su; Minjie Yu; Jiahui Xu; Zhenzhen Yi (Molecular Phylogenetics and Evolution, 2023)

Clonal fragmentation drives performance deterioration of epiphytic and lithophytic ferns in a karst forest - Qian Dai; Yu-Xuan Mo; Quan Chen; Liang Song; Li-Min Zhang; Gbadamassi G.O. Dossa; Hua-Zheng Lu (Flora, 2023)

Evolution characteristic of atmospheric black carbon particles at a coastal site in the Pearl River Delta, China - Jing Wei; Xiao-Feng Huang; Yan Peng; Xiao-Yu Lin; Zhen-Hua Lei; Li-Ming Cao; Wen-Fei Zhu; Song Guo; Ling-Yan He (Environmental Pollution, 2023)

Methane-assisted catalytic light oil desulfurization: Catalyst design, sulfur product distribution analysis and mechanistic study - Hao Xu; Kamran Haddadian; Yimeng Li; Zhaofei Li; Wenping Li; Jack Jarvis; Hua Song (Chemical Engineering Journal, 2023)

Low-temperature and dual-sensing NO2/dimethylamine sensor based on single-crystal WO3 nanoparticles-supported sheets synthesized by simple pyrolysis of spoiled WCl6 powder - Guo-Li Chen; Ming-Song Lv; Li-Li Sui; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

Hydrogeological classification of municipal solid waste landfill sites in China and correlation with groundwater contaminant migration - Liangtong Zhan; Linbo Wu; Hua Han; Shuai Zhang; Honglei Zhou; Xue Song; Li Zhao; Qimeng Guo; Yunmin Chen (Hydrogeology Journal, 2023)

Fungicide exposure accelerated horizontal transfer of antibiotic resistance genes via plasmid-mediated conjugation - Houpu Zhang; Jiajin Song; Zhiruo Zheng; Tongxin Li; Nan Shi; Yuling Han; Luqing Zhang; Yunlong Yu; Hua Fang (Water Research, 2023)

Magnetic ternary layered double hydroxides for efficient removal of 1-naphthalene acetic acid from waters: Adsorption behavior and mechanism - Ti-Bo Fang; Hua Xiao; Ling-Xi Zhao; Na Li; Ling-Yu Luan; Zhao-Xing Yan; Jin-Ming Lin; Ru-Song Zhao (Journal of Environmental Chemical Engineering, 2023)

Development of ic-ELISA and colloidal cold-based immunochromatographic assay for red 2G detection in fruit drinks, red wine, and yoghurts - Xiaoling Li; Xinxin Xu; Lingling Guo; Shanshan Song; Liqiang Liu; Yingyue Zhu; Hua Kuang; Chuanlai Xu; Liguang Xu (Food Bioscience, 2023)

The role of MAPK/NF-κB-associated microglial activation in T-2 toxin-induced mouse learning and memory impairment - Na Li; Chun-Yan Yao; Jun Diao; Xiao-Ling Liu; En-Jie Tang; Qing-Song Huang; Yu-Meng Zhou; Yue-Gu Hu; Xiu-Kuan Li; Jin-Yun Long; Hua Xiao; Da-Wei Li; et al. (Food and Chemical Toxicology, 2023)

Bifunctional non-nucleophilic electrolyte enables long-life magnesium batteries via elimination of passive film on Mg anode - Ruinan Li; Rupeng Zhang; Qingsong Liu; Jiale An; Yajie Song; Biao Deng; Yulin Ma; Hua Huo; Yunzhi Gao; Jiajun Wang; Pengjian Zuo; Geping Yin (Chemical Engineering Journal, 2023)

How much urban air quality is affected by local emissions: A unique case study from a megacity in the Pearl River Delta, China - Meng-Xue Tang; Xiao-Feng Huang; Pei-Ting Yao; Run-Hua Wang; Zhi-Jie Li; Chao-Xi Liang; Xing Peng; Li-Ming Cao; Ke Du; Kuangyou Yu; Song Guo (Atmospheric Environment, 2023)

Lipopolysaccharide-induced endotoxaemia during adolescence promotes stress vulnerability in adult mice via deregulation of nuclear factor erythroid 2-related factor 2 in the medial prefrontal cortex - Yan-chen Chen; Yan-hua Huang; Li Song; Xiao-han Tong; Jun-feng Li; Song Lin; Xi Chen; Ji-chun Zhang; Zi-li Zhang; Qi-yi Zeng (Psychopharmacology, 2023)

Genome-Wide Analysis of the Growth-Regulating Factor Family in Medicago truncatula - Hua Li; Taotao Qiu; Zhaosheng Zhou; Liqing Kang; Rongrong Chen; Liming Zeng; Hongyang Yu; Yihua Wang; Jianbo Song (Journal of Plant Growth Regulation, 2023)

The Analysis of the Glycosyltransferase Gene Function From a Novel Granaticin Producer, Streptomyces Vilmorinianum. YP1 - Shenglan Zheng; Hongling Zhao; Zuoyun Yuan; Xuechen Si; Zongxian Li; Jingyi Song; Yunping Zhu; Hua Wu (Current Microbiology, 2023)

The effects of the CO 2 database on a localized AquaCrop model construction based on a field experiment - Fawen Li; Chunya Song; Hua Li (Irrigation and Drainage, 2023)
To examine whether the use of the default CO 2 database affected the simulation, this paper built AquaCrop models of winter wheat based on the measured CO 2 database and the default CO 2 database. The results showed that the maximum relative error (RE) of the simulated values of biomass and yield under both databases was below 4%, and the residual coefficient method (CRM) and normalized root mean square error (NRMSE) were within ±2%. Compared with the default database, the accuracy under the measured database was higher. To further verify the model, the simulated values of evapotranspiration and soil water content were analysed. The results showed that the RE of evapotranspiration was between 2% and 6% compared with the measured value in the seedling, overwintering and mature periods. In general, the simulated values of evapotranspiration were consistent with the measured values at different irrigation levels. The simulated values of the soil water content were all higher than the measured values, but the simulated results basically reflected the dynamic changes in the soil water content. The results showed that in the absence of measured CO 2 data, the default CO 2 database can be used and the accuracy of the model meets the actual demand.

An all-in-one strategy for municipal solid waste incineration fly ash full resource utilization by heat treatment with added kaolin - Zhijun Song; Xiaowen Zhang; Yujiao Tan; Qin Zeng; Yilong Hua; Xiaoyan Wu; Mi Li; Xudong Liu; Mingliang Luo (Journal of Environmental Management, 2023)

Nanoemulsion: A novel delivery approach for thermosensitive IgG on inhibiting milk fat oxidation - An-Qi Zhang; Meng-Qi Liu; Xiao-Yan Li; Di Xu; Yu-Qi Yin; Nan-Nan Song; Ying-Hua Zhang (Food Research International, 2023)

ShuffleNet-Triplet: A lightweight RE-identification network for dairy cows in natural scenes - Yunfei Wang; Xingshi Xu; Zheng Wang; Rong Li; Zhixin Hua; Huaibo Song (Computers and Electronics in Agriculture, 2023)

E3D: An efficient 3D CNN for the recognition of dairy cow's basic motion behavior - Yunfei Wang; Rong Li; Zheng Wang; Zhixin Hua; Yitao Jiao; Yuanchao Duan; Huaibo Song (Computers and Electronics in Agriculture, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Distribution and weathering characteristics of microplastics in paddy soils following long-term mulching: A field study in Southwest China - Jie Yang; Kaifu Song; Chen Tu; Lianzhen Li; Yudong Feng; Ruijie Li; Hua Xu; Yongming Luo (Science of The Total Environment, 2023)

Electrochemical disinfection may increase the spread of antibiotic resistance genes by promoting conjugal plasmid transfer - Hua Li; Arnaud Dechesne; Zhiming He; Marlene Mark Jensen; Hai Liang Song; Barth F. Smets (Science of The Total Environment, 2023)

Non-thermal plasma assisted catalytic water splitting for clean hydrogen production at near ambient conditions - Wenping Li; Mingyuan Cao; Shijun Meng; Zhaofei Li; Hao Xu; Lijia Liu; Hua Song (Journal of Cleaner Production, 2023)

Solvent-free oxidation of toluene to benzaldehyde using electron-rich Au clusters confined in Silicalite-1 - He Huang; Huahua Fan; Yuzhen Ge; Wanyue Ye; Yingcen Liu; Caicheng Song; Hua Lin; Xiaotong Zhang; Bing Li; Xiaowa Nie; Shufen Zhang; Rongwen Lu (Chemical Engineering Journal, 2023)

Production of low carbon number olefins from natural gas: Methane-involved catalytic non-oxidative propane dehydrogenation - Hao Xu; Mingyuan Cao; Zhaofei Li; Wenping Li; Shijun Meng; Hua Song (Chemical Engineering Journal, 2023)

Correction to: Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2023)

Evaluation on prevention and treatment of cuminaldehyde in culture of shrimp against white spot syndrome virus - Xu Zhang; Li-Hua Hu; Da-Wei Song; Yang Hu; Jiong Chen (Aquaculture, 2023)

Joint role of land cover types and microbial processing on molecular composition of dissolved organic matter in inland lakes - Zhicheng Hong; Hua Ma; Ting Zhang; Qianru Wang; Yilin Chang; Yingyue Song; Zhe Li; Fuyi Cui (Science of The Total Environment, 2023)

Rapid and sensitive detection of quizalofop-p-ethyl by gold nanoparticle-based lateral flow immunoassay in agriproducts and environmental samples - Xue Liu; Jiao Li; Yue Huang; Zhongrong Zhang; Qing Lin; Pengliang Xia; Fanyu Kong; Jun Qiu; Song Fang; Xiude Hua (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Effects of urban particulate matter on gut microbiome and partial schizophrenia-like symptoms in mice: Evidence from shotgun metagenomic and metabolomic profiling - Weizhuo Yi; Yifu Ji; Hua Gao; Shengyong Luo; Rubing Pan; Jian Song; Yangyang He; Yuxuan Li; Yudong Wu; Shuangshuang Yan; Yunfeng Liang; Xiaoni Sun; et al. (Science of The Total Environment, 2023)

Coordination engineering strategy of iron single-atom catalysts boosts anti-Cu(II) interference detection of As(III) with a high sensitivity - Pei-Hua Li; Zong-Yin Song; Xiang-Yu Xiao; Bo Liang; Meng Yang; Shi-Hua Chen; Wen-Qing Liu; Xing-Jiu Huang (Journal of Hazardous Materials, 2023)

Comparative study of hydrodeoxygenation performance over Ni and Ni2P catalysts for upgrading of lignin-derived phenolic compound - Tianhan Zhu; Kun Liu; Haiyong Wang; Jing Wang; Feng Li; Chenguang Wang; Hua Song (Fuel, 2023)

Association between ambient carbon monoxide levels and hospitalization costs of patients with myocardial infarction: Potential effect modification by ABO blood group - Qing-Song Huang; Lai-Xin Zhou; Li-Li Yang; Yue-Xu Jiang; Hua Xiao; Da-Wei Li; Yu-Meng Zhou; Yue-Gu Hu; Na Li; Ya-Fei Li; Ai-Ling Ji; Peng Luo; et al. (Environmental Research, 2023)

Passivation of positively charged cationic defects in perovskite with nitrogen-donor crown ether enabling efficient perovskite solar cells - Yuxuan Yang; Tao Zhao; Ming-Hua Li; Xiaoxue Wu; Mingyue Han; Shih-Chi Yang; Qiaoling Xu; Lede Xian; Xiang Chi; Ning-Jiu Zhao; Hong Cui; Sihan Li; et al. (Chemical Engineering Journal, 2023)

Analysis of Agglomerate Fog Meteorological Characteristics in Anhui Province Based on Traffic Accident Data - Jingjing Gao; Hua Tian; Aixun Li; Jianyang Song; Xiaoxiang Zhu (Pure and Applied Geophysics, 2023)
Using the data of five agglomerate-fog-related traffic accidents during 2014–2017 and fog-related expressway accidents during 2013–2018 assessed by the Anhui provincial traffic authorities and corresponding meteorological observation data, this article analyzes the spatio-temporal characteristics, geographical environment and weather background of agglomerate-fog-related accidents in detail and identifies the characteristics of changes in terms of visibility, humidity, temperature and wind when agglomerate fog occurs. Furthermore, an agglomerate fog forecast index has been established in Anhui Province to provide a reference basis for the agglomerate fog forecast, early warning and prevention.

Establishment of adventitious root culture system of Cynanchum wilfordii in air-lift bioreactors for the efficient production of bioactive compounds - Mei Wang; Miao Wang; Dong An; Chun-Hua Wu; Guang Li; Wei Wang; Xiao-Song Zhang; Mei-Lan Lian (In Vitro Cellular & Developmental Biology - Plant, 2022)

Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2022)

Association between gestational arsenic exposure and intrauterine growth restriction: the role of folate content - Fei-Xiang Xu; Xu Chen; Heng Zhang; Yi-Jun Fan; Ya-Ping Song; Jin-Wei Lv; Ya-Li Xie; Yichao Huang; Dao-Zhen Chen; Hua Wang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

Effects of plant morphology, vitamin C, and other co-present pesticides on the deposition, dissipation, and metabolism of chlorothalonil in pakchoi - Guolei Shan; Meiqing Zhu; Dong Zhang; Taozhong Shi; Jialong Song; Qing X. Li; Rimao Hua (Environmental Science and Pollution Research, 2022)

Comprehensive comparison of the prognostic value of systemic inflammation biomarkers for cancer cachexia: a multicenter prospective study - Hailun Xie; Guotian Ruan; Lishuang Wei; Heyang Zhang; Yizhong Ge; Qi Zhang; Shiqi Lin; Mengmeng Song; Xi Zhang; Xiaoyue Liu; Ming Yang; Meng Tang; et al. (Inflammation Research, 2022)

Surface urban heat island and its relationship with land cover change in five urban agglomerations in China based on GEE - Hua Zhang; Yuxin Yin; Huimin An; Jinping Lei; Ming Li; Jinyue Song; Wuhong Han (Environmental Science and Pollution Research, 2022)

Identification of thioredoxin genes and analysis of their expression under abiotic stresses in Medicago truncatula - Liugen Xu; Yong Zhou; Jie Cheng; Liqing Kang; Yuqi Qiang; Xuemei Yan; Yuhua Yan; Ying Tang; Yihua Wang; Hua Li; Jianbo Song (Acta Physiologiae Plantarum, 2022)

The association between short-term ambient sulfur dioxide exposure and hospitalization costs of ischemic stroke: a hospital-based study in Chongqing, China - En-Jie Tang; Yu-Meng Zhou; Li-Li Yang; Nan Wang; Yue-Xu Jiang; Hua Xiao; Yue-Gu Hu; Da-Wei Li; Na Li; Qing-Song Huang; Ning Du; Ya-Fei Li; et al. (Environmental Science and Pollution Research, 2022)

Assessment of paddy expansion impact on regional climate using WRF model: a case study in Sanjiang Plain, Northeast China - Peng Huang; Dan Li; Hua Xie; Chaoli Liu; Hayat Ullah; Yang Xu; Changhong Song; Chunsheng Dai; Yuanlai Cui; Yufeng Luo (Theoretical and Applied Climatology, 2022)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Numerical and experimental investigation on hydrodynamic performance of the stick-held dip net in Pacific saury fishery - Fei Li; Liming Song; Chuanxiang Hua; Qingcheng Zhu (Frontiers in Marine Science, 2022)
Stick-held dip (SHD) net is an effective fishing gear target for catching the Pacific saury. In this study, the hydrodynamic performance of an SHD net in current was investigated by means of numerical simulation and experimental test, and a mathematical model based on the lumped-mass method and principle of rigid body kinematics was developed to predict the net shape and tension of the cable. A series of physical model tests based on Tauti’s law and full-scale measurements at sea were conducted to evaluate the applicability of the numerical model. The results showed that the prediction performance of the numerical model was good, with a mean relative error of approximately 20% among the numerical, experimental, and field measured data. The dynamic shooting behavior of the SHD net at different current velocities and the effects of the length of the hauling rope and the mesh size on the net shape and tension of the cable were analyzed using the numerical simulation approach. When the current velocity increased from 0.12 to 0.46 m/s, the enclosed volume of the SHD net decreased by 62.9%. The height of net opening increased by 9.29% to 13.53% for every 10% increase in the length of the hauling rope from 0.96 to 1.44 m. With the increase in mesh size from 24 to 30 and 35 mm, the sinking depth and speed of the net increased, and the tension force of the cables decreased by 9.02% and 12.10%, respectively. The results suggested that (1) the numerical model could realistically represent the hydrodynamic characteristics of the SHD net; (2) the suitable operation current velocity is below 0.60 m/s; (3) the reasonable length of the hauling rope is about 30 m; and (4) the mesh size of the main netting could be increased to 30 mm.

Comparative Analysis of Endogenous Hormones and Metabolite Profiles in Early-Spring Flowering Plants and Unflowered Plants Revealing the Strategy of Blossom - Xue Yan; Jia Liu; Ke-Xin Wu; Nan Yang; Li-Ben Pan; Ying Song; Yang Liu; Zhong-Hua Tang (Journal of Plant Growth Regulation, 2022)

Loss of anthocyanidin synthase gene is associated with white flowers of Salvia miltiorrhiza Bge. f. alba, a natural variant of S. miltiorrhiza - Caicai Lin; Piyi Xing; Hua Jin; Changhao Zhou; Xingfeng Li; Zhenqiao Song (Planta, 2022)

Combined System of Organic Substrate and Straw-Degrading Microbial Agents Improved Soil Organic Matter Levels and Microbial Abundance in a Rice–Wheat Rotation - Shi-Li Song; Xue Luo; Hao Wu; Xiao-Lin Lu; Fang-Ji Xu; Zhen-Hua Zhang; Yong-Xiang Guan; Chuan-Chao Dai (Current Microbiology, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

The genes for sensory perception of sound should be considered in gene diagnosis of congenital sensorineural hearing loss and microtia - Ken Lin; Ding-Yun You; Li-Huan Zhang; Li-Juan Zhou; Jin-Yan Zu; Yang Xiao; Mei-Hua Sun; Dong-Su; Xue Cao; Tie-Song Zhang; Jing Ma (Journal of Applied Genetics, 2022)

Efficient production of GlcNAc in an aqueous-organic system with a Chitinolyticbacter meiyuanensis SYBC-H1 mutant - Zhi-kui Hao; Jian-song Li; Dan-hua Wang; Fei He; Jing-shi Xue; Liang-hong Yin; Hua-bao Zheng (Biotechnology Letters, 2022)

Unexpected role of electron‐transfer hub in direct degradation of pollutants by exoelectrogenic bacteria - Ting‐Ting Zhu; Zhou‐Hua Cheng; Sheng‐Song Yu; Wen‐Wei Li; Dong‐Feng Liu; Han‐Qing Yu (Environmental Microbiology, 2022)
Summary Exoelectrogenic bacteria (EEB) are capable of anaerobic respiration with diverse extracellular electron acceptors including insoluble minerals, electrodes and flavins, but the detailed electron transfer pathways and reaction mechanisms remain elusive. Here, we discover that CymA, which is usually considered to solely serve as an inner‐membrane electron transfer hub in Shewanella oneidensis MR‐1 (a model EEB), might also function as a reductase for direct reducing diverse nitroaromatic compounds (e.g. 2,4‐dichloronitrobenzene) and azo dyes. Such a process can be accelerated by dosing anthraquinone‐2,6‐disulfonate. The CymA‐based reduction pathways in S . oneidensis MR‐1 for different contaminants could be functionally reconstructed and strengthened in Escherichia coli . The direct reduction of lowly polar contaminants by quinol oxidases like CymA homologues might be universal in diverse microbes. This work offers new insights into the pollutant reduction mechanisms of EEB and unveils a new function of CymA to act as a terminal reductase.

A 250 m resolution global leaf area index product derived from MODIS surface reflectance data - Zhiqiang Xiao; Jinling Song; Hua Yang; Rui Sun; Juan Li (International Journal of Remote Sensing, 2022)

Assessing the fractionation and bioavailability of heavy metals in soil–rice system and the associated health risk - Yuanyuan Wang; Weiwei Xu; Jizhou Li; Yinxian Song; Ming Hua; Wenbo Li; Yubo Wen; Tianyuan Li; Xinxing He (Environmental Geochemistry and Health, 2022)

Fine mapping and candidate gene analysis of qGSN5, a novel quantitative trait locus coordinating grain size and grain number in rice - Hua Yuan; Peng Gao; Xiaoling Hu; Min Yuan; Zhengyan Xu; Mengya Jin; Wencheng Song; Shijie Zhan; Xiaobo Zhu; Bin Tu; Ting Li; Yuping Wang; et al. (Theoretical and Applied Genetics, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Yak Excreta Application Alter Nitrification by Regulating the Ammonia-Oxidizing Bacterial Communities in Wetland Soils - Li Chen; Rong Bo Zheng; Jun Qin Gao; Ming Hua Song; Xue Lian Guo (Journal of Soil Science and Plant Nutrition, 2021)

Correction to: AGGF1 protects from myocardial ischemia/reperfusion injury by regulating myocardial apoptosis and angiogenesis - Yu Liu; Hui Yang; Lina Song; Nan Li; Qiu-Yue Han; Cui Tian; Erhe Gao; Jie Du; Yun-Long Xia; Hui-Hua Li (Apoptosis, 2021)

Polysaccharide from Caulerpa lentillifera : extraction optimization with response surface methodology, structure and antioxidant activities - Hua Tian; Haifang Liu; Weikang Song; Li Zhu; Xueqiong Yin (Natural Product Research, 2021)

Tissue distribution of SARS-CoV-2 in non-human primates after combined intratracheal and intranasal inoculation - Tian-Zhang Song; Jian-Bao Han; Xiang Yang; Ming-Hua Li; Yong-Tang Zheng (Science China Life Sciences, 2021)

Identification of RNA helicases in Medicago truncatula and their expression patterns under abiotic stress - Jie Cheng; Songsong Zhou; Kun Yang; Hongyang Yu; Rongrong Chen; Liming Zeng; Hua Li; Yihua Wang; Jianbo Song (Physiology and Molecular Biology of Plants, 2021)

Sandaracinobacteroides hominis gen. nov., sp. nov., isolated from human skin - Ping-Hua Qu; Hai-Min Luo; Jun-Hui Feng; Song Li; Cha Chen; Lei Dong; Yu-Zhen Ming; Wen-Jun Li; Ying Lin (Archives of Microbiology, 2021)

On the origin of SARS-CoV-2—The blind watchmaker argument - Chung-I Wu; Haijun Wen; Jian Lu; Xiao-dong Su; Alice C. Hughes; Weiwei Zhai; Chen Chen; Hua Chen; Mingkun Li; Shuhui Song; Zhaohui Qian; Qihui Wang; et al. (Science China Life Sciences, 2021)

CRWS-mountain Project: Coordinate remediation techniques and devices for water-soil pollution in mountain areas in China - Ling Song; Lei Li; Chao-jie Zhang; Li Huang; Jin-song Guo; Bo Zhu; Ming-hua Zhou (Journal of Mountain Science, 2021)

An effective interpolation strategy for mitigating the day boundary discontinuities of precise GNSS orbit products - Chuanfeng Song; Hua Chen; Weiping Jiang; Xiangdong An; Qusen Chen; Wudong Li (GPS Solutions, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Petrogenesis of the early Permian A-type granites in the Halajun region, southwest Tianshan, western Xinjiang, NW China: implications for geodynamics of Tarim large igneous province - Zhao-Jian Zong; Yang-Song Du; Shun-Ting Li; Yi Cao; Jing-Guo Du; Xiao-Hua Deng; Li-Wei Xue (International Geology Review, 2021)

Altered structural and functional connectivity in CSF1R-related leukoencephalopathy - Fei-Xia Zhan; Ze-Yu Zhu; Qing Liu; Hai-Yan Zhou; Xing-Hua Luan; Xiao-Jun Huang; Xiao-Li Liu; Wo-Tu Tian; Shi-Ge Wang; Xiao-Xuan Song; Guang Chen; Ming-Liang Zhao; et al. (Brain Imaging and Behavior, 2021)

Optimization of LED fishing lamp allocation based on numerical modeling in Pacific saury fishery - Fei Li; Chuanxiang Hua; Qingcheng Zhu; Liming Song (Fisheries Science, 2021)

A hierarchical object detection method in large-scale optical remote sensing satellite imagery using saliency detection and CNN - Zhina Song; Haigang Sui; Li Hua (International Journal of Remote Sensing, 2021)

Evaluation of the efficacy and safety of hydroxychloroquine in comparison with chloroquine in moderate and severe patients with COVID-19 - Qiuyu Li; Cheng Cui; Fei Xu; Jianping Zhao; Nan Li; Haichao Li; Tianbing Wang; Hua Zhang; Na Liu; Yudong Wei; Xiaoye Niu; Yan Xu; et al. (Science China Life Sciences, 2021)

A novel Schiff base cobalt(III) complex induces a synergistic effect on cervical cancer cells by arresting early apoptosis stage - Wen-Hui Liao; Xue-Qing Song; Yan-Jie Kong; Rui-Dan Bao; Fang-Fang Li; Jie Zhou; Qi-Hua Zhao; Jing-Yuan Xu; Ni Xie; Ming-Jin Xie (BioMetals, 2021)

Correction to: The effect of teprenone on the intestinal morphology and microbial community of Chinese sea bass (Lateolabrax maculatus) under intermittent hypoxic stress - Hong-biao Dong; Yong-xu Sun; Ya-fei Duan; Hua Li; Yong Li; Qing-song Liu; Wen-hao Wang; Jia-song Zhang (Fish Physiology and Biochemistry, 2020)

The Bre1/Rad6 machinery: writing the central histone ubiquitin mark on H2B and beyond - Zhi-Heng Deng; Hua-Song Ai; Cheng-Piao Lu; Jia-Bin Li (Chromosome Research, 2020)

Zircon U-Pb-Hf isotopes and geochemistry of Jurassic igneous rocks from the southern Zhangguangcai Range, NE China: constraints on magmatism, petrogenesis and tectonic implications - Zuo-Zhen Han; Xiang Ren; Hans-Peter Schertl; Xu-Ping Li; Zhi-Gang Song; Qing-Xiang Du; Chao Han; Wen-Jian Zhong; Li-Hua Gao (International Geology Review, 2020)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

The effect of teprenone on the intestinal morphology and microbial community of Chinese sea bass (Lateolabrax maculatus) under intermittent hypoxic stress - Hong-biao Dong; Yong-xu Sun; Ya-fei Duan; Hua Li; Yong Li; Qing-song Liu; Wen-hao Wang; Jia-song Zhang (Fish Physiology and Biochemistry, 2020)

Structural features of an acidic polysaccharide with the potential of promoting osteoblast differentiation from Lycium ruthenicum Murr. - Shu-Qi Wang; Bing Liu; Su Liu; Song-Zi Xie; Li-Hua Pan; Xue-Qiang Zha; Qiang-Ming Li; Jian-Ping Luo (Natural Product Research, 2020)

Hydraulic conductivity characteristics of carbonated reactive magnesia-treated silt - Guang-Hua Cai; Song-Yu Liu; Guang-Yin Du; Liang Wang; Jiang-Shan Li; Lei Liu (Bulletin of Engineering Geology and the Environment, 2020)

Design and synthesis of novel 7-[( N -substituted-thioureidopiperazinyl)-methyl]-camptothecin derivatives as potential cytotoxic agents - Zi-Long Song; Guan-Zhou Yang; Jun-Cai Li; Ying-Qian Liu; Chen-Jie Yang; Masuo Goto; Zhi-Jun Zhang; Susan L. Morris-Natschke; Hua Liu; Kuo-Hsiung Lee (Natural Product Research, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

Interspecific difference in N:P stoichiometric homeostasis drives nutrient release and soil microbial community composition during decomposition - Hanxiong Song; Jingjing Huang; Leming Ge; Changhui Peng; Pengxiang Zhao; Xinyi Guo; Tong Li; Xiaojuan Shen; Qiuan Zhu; Weiguo Liu; Hua Wei; Meng Wang (Plant and Soil, 2020)

A review of progress in coupled ocean-atmosphere model developments for ENSO studies in China - Rong-Hua Zhang; Yongqiang Yu; Zhenya Song; Hong-Li Ren; Youmin Tang; Fangli Qiao; Tongwen Wu; Chuan Gao; Junya Hu; Feng Tian; Yuchao Zhu; Lin Chen; et al. (Journal of Oceanology and Limnology, 2020)

Effect of nutritional factors on the accretion of secondary metabolites in Malaysian ginseng adventitious root cultures - Xi-Hua Cui; Hosakatte Niranjana Murthy; Ji-De Zhang; Hang-Lin Song; Yin-Ji Jiang; Wen-Wen Qi; Yong Yi Li; Kee-Yoeup Paek; So-Young Park (Plant Biotechnology Reports, 2020)

Grazing Offsets Nitrogen Enrichment Effects on Species Richness by Promoting the Random Colonization of Local Species in an Alpine Grassland - Ming-Hua Song; Jin Chen; Xing-Liang Xu; Yi-Kang Li; Jun-Qin Gao; Hua OuYang (Ecosystems, 2020)

Evaluation model of synergy degree for disaster prevention and reduction in coastal cities - Xing Huang; Junyi Song; Xing Li; Hua Bai (Natural Hazards, 2020)

The application of the ‘Gene-deletor’ technology in banana - Chun-hua Hu; Qiao-song Yang; Xiu-hong Shao; Tao Dong; Fang-cheng Bi; Chun-yu Li; Gui-ming Deng; Yi Li; Gan-jun Yi; Tong-xin Dou (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Banana ( Musa spp.) is an important tropical crop. Banana industry is under biotic and abiotic stresses such as Fusarium wilt, typhoon, cold stress. Genetic engineering offers a powerful strategy to create germplasm of banana with enhanced resistance. The safety of genetically modified organisms has become a bottleneck restricting the popularization and application of genetically modified technology. In this study, a candidate promoter, LEAFY (LFY) for expression and flower initiation in Arabidopsis , was cloned and constructed to ‘Gene-deletor’ vector. Histochemical β-glucuronidase (GUS) staining results showed that the ‘Gene-deletor’ vector driven by LFY promoter could lead to 88.5% excision efficiency from Arabidopsis seeds based on more than 200 T 3 progeny examined per event. GUS staining was found to be partially negative in transgenic bananas, however, polymerase chain reaction could still detect the presence of large fragments of the vector. These results suggest that although LFY promoter could not completely drive the ‘Gene-deletor’ vector to achieve the effect of complete elimination of exogenous gene in bananas, its efficiency of eliminating exogenous gene laid a theoretical foundation for cloning banana fruit-specific promoters, that is, ‘non-transgenic’ GM bananas.

Isoflurane produces antidepressant effects inducing BDNF-TrkB signaling in CUMS mice - Sha-Sha Zhang; Yu-Hua Tian; Song-Jun Jin; Wen-Cheng Wang; Jing-Xin Zhao; Xiao-Ming Si; Li Zhang; Hong Xu; Jing-Yu Jin (Psychopharmacology, 2019)

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Low temperature culture enhances ameloblastic differentiation of human keratinocyte stem cells - Yingnan Song; Bingmei Wang; Hua Li; Xiaoxiao Hu; Xin Lin; Xuefeng Hu; Yanding Zhang (Journal of Molecular Histology, 2019)

Three Tibetan grassland plant species tend to partition niches with limited plasticity in nitrogen use - Li Zhang; Rui Pang; Xingliang Xu; Minghua Song; Yikang Li; Huakun Zhou; Xiaoyong Cui; Yanfen Wang; Hua Ouyang (Plant and Soil, 2019)

miR-30a reverses TGF-β2-induced migration and EMT in posterior capsular opacification by targeting Smad2 - Hua Li; Hui Song; Xiaoyong Yuan; Jun Li; Hua Tang (Molecular Biology Reports, 2019)

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

Selenium-Yeast Alleviated Inflammatory Damage Caused by Lead via Inhibiting Ras/ERK Pathway and Inflammatory Factors in Chicken Skeletal Muscles - Zhe Liu; Feng Zhang; Ping Lu; Rui Zhao; Hua Zhang; Baifen Song; Liyang Li; Zhijun Wu; Rui Wu (Biological Trace Element Research, 2019)

Long-term straw mulch effects on crop yields and soil organic carbon fractions at different depths under a no-till system on the Chengdu Plain, China - Zijun Zhou; Xiangzhong Zeng; Kun Chen; Zhu Li; Song Guo; Yuxian Shangguan; Hua Yu; Shihua Tu; Yusheng Qin (Journal of Soils and Sediments, 2019)

The Toxicological Effects of Mercury Exposure in Marine Fish - Na Zheng; Sujing Wang; Wu Dong; Xiuyi Hua; Yunyang Li; Xue Song; Qingwen Chu; Shengnan Hou; Yang Li (Bulletin of Environmental Contamination and Toxicology, 2019)

A remote sensing method for retrieving land surface emissivity and temperature in cloudy areas: a case study over South China - Fang-Cheng Zhou; Zhao-Liang Li; Hua Wu; Si-Bo Duan; Xiaoning Song; Guangjian Yan (International Journal of Remote Sensing, 2019)

Correction to: Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

The fecal virome of red-crowned cranes - Yan Wang; Shixing Yang; Dawei Liu; Chenglin Zhou; Wang Li; Yuan Lin; Xiaochun Wang; Quan Shen; Hua Wang; Chuang Li; Minghui Zong; Yuzhu Ding; et al. (Archives of Virology, 2019)

Boron Affects the Development of the Kidney Through Modulation of Apoptosis, Antioxidant Capacity, and Nrf2 Pathway in the African Ostrich Chicks - Haseeb Khaliq; Wang Jing; Xiao Ke; Yang Ke-Li; Sun Peng-peng; Lei Cui; Qiu Wei-wei; Lei Zhixin; Liu Hua-Zhen; Song Hui; Zhong Ju-Ming; Peng Ke-Mei (Biological Trace Element Research, 2018)

Three new 3,4-seco-cycloartane triterpenes from Gardenia sootepensis - Wei-Wu Song; Xue-Qin Wang; Hua-Li Jia; Zheng-Kun Zhang; Yong-Jie Ding; Ya-Hong Chen (Natural Product Research, 2018)

First report of Pseudomonas marginalis isolated from celery with symptom of stem rot in China - Xiaoying Li; Yu Tian; Li Song; Hua Xie (Journal of Plant Pathology, 2018)

A Dual-Replicon Shuttle Vector System for Heterologous Gene Expression in a Broad Range of Gram-Positive and Gram-Negative Bacteria - Mingxi Hua; Jingjing Guo; Min Li; Chen Chen; Yuanyuan Zhang; Chuan Song; Dong Jiang; Pengcheng Du; Hui Zeng (Current Microbiology, 2018)

Influence of deflection angles on flow behaviours in openchannel bends - Bing-dong Li; Xin-hua Zhang; Han-song Tang; Ryota Tsubaki (Journal of Mountain Science, 2018)

Soil infiltration processes of different underlying surfaces in the permafrost region on the Tibetan Plateau - Guo-jie Hu; Li-ming Tian; Lin Zhao; Xiao-dong Wu; Ren Li; Tong-hua Wu; Xiao-fan Zhu; Er-ji Du; Zhi-wei Wang; Jun-ming Hao; Wang-ping Li; Song-he Wang (Hydrological Sciences Journal, 2018)

Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Social Isolation During Adolescence Induces Anxiety Behaviors and Enhances Firing Activity in BLA Pyramidal Neurons via mGluR5 Upregulation - Song Lin; Xin Li; Yi-Hua Chen; Feng Gao; Hao Chen; Neng-Yuan Hu; Lang Huang; Zheng-Yi Luo; Ji-Hong Liu; Qiang-Long You; Ya-Nan Yin; Ze-Lin Li; et al. (Molecular Neurobiology, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Effects of Boron Supplementation on Expression of Hsp70 in the Spleen of African Ostrich - Khaliq Haseeb; Jing Wang; Ke Xiao; Ke-li Yang; Peng-peng Sun; Xing-tong Wu; You Luo; Hui Song; Hua-zhen Liu; Ju-ming Zhong; Ke-mei Peng (Biological Trace Element Research, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Long-term grazing affects relationships between nitrogen form uptake and biomass of alpine meadow plants - Yu Guo; Li-Ping Liu; Li-Li Zheng; Fei-Hai Yu; Ming-Hua Song; Xian-Zhou Zhang (Plant Ecology, 2017)

Fasudil Enhances Therapeutic Efficacy of Neural Stem Cells in the Mouse Model of MPTP-Induced Parkinson’s Disease - Yan-Hua Li; Jing-Wen Yu; Jian-Yin Xi; Wen-Bo Yu; Jian-Chun Liu; Qing Wang; Li-Juan Song; Ling Feng; Ya-Ping Yan; Guang-Xian Zhang; Bao-Guo Xiao; Cun-gen Ma (Molecular Neurobiology, 2017)

Estimating environmental value losses from earth materials excavation and infilling for large-scale airport construction: a case of Dalian Offshore Airport, Dalian, China - Hua-Kun Yan; Nuo Wang; Nuan Wu; Nan-Qi Song; Dao-Li Zhu (Environmental Science and Pollution Research, 2017)

Development of a Semi-nested PCR-Based Method for Specific and Rapid Detection of Alternaria solani Causing Potato Early Blight in Soil - Qing Gu; Zhi-Hui Yang; Dong-Mei Zhao; Dai Zhang; Qian Wang; Li-Song Ma; Jie-Hua Zhu (Current Microbiology, 2017)

Phenotypic Variation and Genetic Diversity in the Collections of Erianthus Arundinaceus (Retz.) Jesw. - Xi-Hui Liu; Huan-Zhong Song; Ge-Min Zhang; Wei-Xing Duan; Rong-Hua Zhang; Yang-Rui Li (Sugar Tech, 2017)

An RNA-Seq transcriptome analysis revealing novel insights into aluminum tolerance and accumulation in tea plant - Yong Li; Jie Huang; Xiaowei Song; Ziwei Zhang; Ye Jiang; Yulu Zhu; Hua Zhao; Dejiang Ni (Planta, 2017)

Association of GWAS-Reported Variant rs11196288 near HABP2 with Ischemic Stroke in Chinese Han Population - Shao-hua Li; Chang-he Shi; Yu-sheng Li; Fang Li; Mi-bo Tang; Xin-jing Liu; Shuo Zhang; Zhi-lei Wang; Bo Song; Yu-ming Xu (Journal of Molecular Neuroscience, 2017)

Rapid quantification of multi-components in alcohol precipitation liquid of Codonopsis Radix using near infrared spectroscopy (NIRS) - Yu Luo; Wen-long Li; Wen-hua Huang; Xue-hua Liu; Yan-gang Song; Hai-bin Qu (Journal of Zhejiang University-SCIENCE B, 2017)

The septin protein S ep4 facilitates host infection by plant fungal pathogens via mediating initiation of infection structure formation - Hui‐Qiang Feng; Gui‐Hua Li; Shun‐Wen Du; Song Yang; Xue‐Qian Li; Paul de Figueiredo; Qing‐Ming Qin (Environmental Microbiology, 2017)
Summary Many phytopathogenic fungi use infection structures (IFSs, i.e., appressoria and infection cushions) to penetrate host cuticles. However, the conserved mechanisms that mediate initiation of IFS formation in divergent pathogens upon sensing the presence of host plants remain obscure. Here, we demonstrate that a conserved septin gene SEP4 plays crucial roles in this process. Disruption of SEP4 in the plant grey mould fungus Botrytis cinerea completely blocked IFS formation and abolished the virulence of Δ Bcsep4 mutants on unwounded hosts. During IFS formation, mutants lacking SEP4 could produce reactive oxygen species (ROS) normally. Inhibition of ROS production in strains harbouring the SEP4 gene resulted in disordered assembly of Sep4 and the subsequent failure to form infection cushions, suggesting that proper Sep4 assembly regulated by ROS is required for initiation of IFS formation and infection. Moreover, loss of SEP4 severely impaired mutant conidiation, melanin and chitin accumulation in hyphal tips and lesion expansion on wounded hosts, but significantly promoted germ tube elongation and sclerotium production. SEP4 ‐mediated fungal pathogenic development, including IFS formation, was validated in the hemibiotroph Magnaporthe oryzae . Our findings indicate that Sep4 plays pleiotropic roles in B. cinerea development and specifically facilities host infection by mediating initiation of IFS formation in divergent plant fungal pathogens in response to ROS signaling.

Aminopeptidase N5 (APN5) as a Putative Functional Receptor of Cry1Ac Toxin in the Larvae of Athetis lepigone - Li-yu Wang; Shao-hua Gu; Zi-yan Nangong; Ping Song; Qin-ying Wang (Current Microbiology, 2017)

MicroRNA-15b silencing inhibits IL-1β-induced extracellular matrix degradation by targeting SMAD3 in human nucleus pulposus cells - Liang Kang; Cao Yang; Huipeng Yin; Kangcheng Zhao; Wei Liu; Wenbin Hua; Kun Wang; Yu Song; Ji Tu; Shuai Li; Rongjin Luo; Yukun Zhang (Biotechnology Letters, 2017)

Analysis of elastic anisotropy of tight sandstone and the influential factors - Lian-Teng Song; Zhong-Hua Liu; Can-Can Zhou; Jun Yu; Li-Jun Xiu; Zhong-Chun Sun; Hai-Tao Zhang (Applied Geophysics, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Genetic variation in mitochondrial genes of the tick Haemaphysalis flava collected from wild hedgehogs in China - Zhong-Bo Li; Tian-Yin Cheng; Xing-Li Xu; Lu-Lin Song; Guo-Hua Liu (Experimental and Applied Acarology, 2017)

RAS Promotes Proliferation and Resistances to Apoptosis in Meningioma - Chunling Jiang; Tao Song; Jingao Li; Fan Ao; Xiaochang Gong; Yicheng Lu; Chenran Zhang; Liangyu Chen; Yunhui Liu; Hua He; Ouping Huang (Molecular Neurobiology, 2017)

Inhibition of microRNA-181a may suppress proliferation and invasion and promote apoptosis of cervical cancer cells through the PTEN/Akt/FOXO1 pathway - Hongmei Xu; Jihong Zhu; Cong Hu; Hua Song; Yiyang Li (Journal of Physiology and Biochemistry, 2016)

Synergistic and Superimposed Effect of Bone Marrow-Derived Mesenchymal Stem Cells Combined with Fasudil in Experimental Autoimmune Encephalomyelitis - Jing-Wen Yu; Yan-Hua Li; Guo-Bin Song; Jie-Zhong Yu; Chun-Yun Liu; Jian-Chun Liu; Hai-Fei Zhang; Wan-Fang Yang; Qing Wang; Ya-Ping Yan; Bao-Guo Xiao; Cun-Gen Ma (Journal of Molecular Neuroscience, 2016)

Degradation properties of various macromolecules of cultivable psychrophilic bacteria from the deep-sea water of the South Pacific Gyre - Li Zhang; Yan Wang; Jing Liang; Qinghao Song; Xiao-Hua Zhang (Extremophiles, 2016)

Metabolic engineering of Corynebacterium glutamicum for methionine production by removing feedback inhibition and increasing NADPH level - Ying Li; Hua Cong; Bingnan Liu; Jinzhu Song; Xueying Sun; Junzheng Zhang; Qian Yang (Antonie van Leeuwenhoek, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Photosynthetic and growth responses of Schima superba seedlings to sulfuric and nitric acid depositions - Fang-fang Yao; Hui-ming Ding; Li-li Feng; Jing-jing Chen; Song-yu Yang; Xi-hua Wang (Environmental Science and Pollution Research, 2016)

Spatial Variations of Soil Microbial Activities in Saline Groundwater-Irrigated Soil Ecosystem - Li-Juan Chen; Qi Feng; Chang-Sheng Li; You-Xi Song; Wei Liu; Jian-Hua Si; Bao-Gui Zhang (Environmental Management, 2016)

MpMYBS3 as a crucial transcription factor of cold signaling confers the cold tolerance of banana - Tong-xin Dou; Chun-hua Hu; Xiao-xuan Sun; Xiu-hong Shao; Jun-hua Wu; Li-jie Ding; Jie Gao; Wei-di He; Manosh-Kumar Biswas; Qiao-song Yang; Gan-jun Yi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The SIRT1 inhibitor, nicotinamide, inhibits hepatitis B virus replication in vitro and in vivo - Wan-Yu Li; Ji-Hua Ren; Na-Na Tao; Long-Kuan Ran; Xiang Chen; Hong-Zhong Zhou; Bo Liu; Xiao-Song Li; Ai-Long Huang; Juan Chen (Archives of Virology, 2016)

JA, a new type of polyunsaturated fatty acid isolated from Juglans mandshurica Maxim, limits the survival and induces apoptosis of heptocarcinoma cells - Xiu-Li Gao; Hua Lin; Wei Zhao; Ya-Qin Hou; Yong-Li Bao; Zhen-Bo Song; Lu-Guo Sun; Shang-Yi Tian; Biao Liu; Yu-Xin Li (Apoptosis, 2016)

Programmed Death Ligand-1 on Microglia Regulates Th1 Differentiation via Nitric Oxide in Experimental Autoimmune Encephalomyelitis - Jingxia Hu; Hao He; Zhengang Yang; Guangming Zhu; Li Kang; Xiuli Jing; Hai Lu; Wengang Song; Bo Bai; Hua Tang (Neuroscience Bulletin, 2016)

Effects of rosiglitazone on proliferation and differentiation of duck preadipocytes - Fang Ding; Jiamin Qiu; Qingqing Li; Jiwei Hu; Chenling Song; Chunchun Han; Hua He; Jiwen Wang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Screening and identification of organics-degrading bacteria from the sediment of sea cucumber Apostichopus japonicus ponds - Dongsheng Zhang; Hua Li; Yang Liu; Guo Qiao; Shuang Chi; Jian Song (Aquaculture International, 2016)

Elevated Serum Mannose-Binding Lectin Levels Are Associated with Poor Outcome After Acute Ischemic Stroke in Patients with Type 2 Diabetes - Fang-Yu Song; Meng-Hai Wu; Li-hua Zhu; Zhi-Qiang Zhang; Qin-De Qi; Chang-li Lou (Molecular Neurobiology, 2015)

Characteristics of gravity anomalies and prediction of volcanosedimentary boron deposit distribution in the Xiongba area, Tibet - Li-Rong Song; Chang-Qing Yu; Gui-Hua Li; Yang-Yang Feng; Jun-Jie He (Applied Geophysics, 2015)

Genome-wide identification of allele-specific expression in response to Streptococcus suis 2 infection in two differentially susceptible pig breeds - Huayu Wu; Uma Gaur; Supamit Mekchay; Xianwen Peng; Lianghua Li; Hua Sun; Zhongxu Song; Binke Dong; Mingbo Li; Klaus Wimmers; Siriluck Ponsuksili; Kui Li; et al. (Journal of Applied Genetics, 2015)

Bacterial growth efficiency in a partly eutrophicated bay of South China Sea: Implication for anthropogenic impacts and potential hypoxia events - Xing-Yu Song; Hua-Xue Liu; Yu Zhong; Ye-Hui Tan; Geng Qin; Kai-Zhi Li; Ping-Ping Shen; Liang-Min Huang; You-Shao Wang (Ecotoxicology, 2015)

Plasticity in nitrogen form uptake and preference in response to long-term nitrogen fertilization - Ming-Hua Song; Li-Li Zheng; Katharine N. Suding; Tan-Feng Yin; Fei-Hai Yu (Plant and Soil, 2015)

DNA methylation level of promoter region of activating transcription factor 5 in glioma - Xiao-min Hua; Juan Wang; Dong-meng Qian; Jing-yi Song; Hao Chen; Xiu-li Zhu; Rui Zhou; Yu-dan Zhao; Xiu-zhi Zhou; Ling Li; Li Zhang; Xu-xia Song; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Assessing the early changes of cerebral glucose metabolism via dynamic 18FDG-PET/CT during cardiac arrest - Ying-Qing Li; Xiao-Xing Liao; Jian-Hua Lu; Rong Liu; Chun-Lin Hu; Gang Dai; Xiang-Song Zhang; Xin-Chong Shi; Xin Li (Metabolic Brain Disease, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

Water relations and gas exchange of fan bryophytes and their adaptations to microhabitats in an Asian subtropical montane cloud forest - Liang Song; Yong-Jiang Zhang; Xi Chen; Su Li; Hua-Zheng Lu; Chuan-Sheng Wu; Zheng-Hong Tan; Wen-Yao Liu; Xian-Meng Shi (Journal of Plant Research, 2015)

Hydrochemistry of the natural low pH groundwater in the coastal aquifers near Beihai, China - Xun Zhou; Ye Shen; Hua Zhang; Chao Song; Jingwei Li; Yan Liu (Journal of Ocean University of China, 2015)

QTL mapping for salt tolerance based on snp markers at the seedling stage in maize (Zea mays L.) - Dezhou Cui; Dandan Wu; Yamuna Somarathna; Chunyan Xu; Song Li; Peng Li; Hua Zhang; Huabang Chen; Li Zhao (Euphytica, 2015)

Endogenous nitric oxide in Pseudomonas fluorescens ZY2 as mediator against the combined exposure to zinc and cefradine - Yan-Bin Xu; Yan Zhou; Jing-Jing Ruan; Shi-Hui Xu; Ji-Dong Gu; Shao-Song Huang; Li Zheng; Bao-Hong Yuan; Li-Hua Wen (Ecotoxicology, 2015)

Deletion of d-ribulose-5-phosphate 3-epimerase (RPE1) induces simultaneous utilization of xylose and glucose in xylose-utilizing Saccharomyces cerevisiae - Ming-Hua Shen; Hao Song; Bing-Zhi Li; Ying-Jin Yuan (Biotechnology Letters, 2015)

Association between the CYP2E1 polymorphisms and lung cancer risk: a meta-analysis - Xiang-Hua Ye; Liang Song; Ling Peng; Zhibin Bu; Sen-Xiang Yan; Jie Feng; Xin-Li Zhu; Xin-Biao Liao; Xue-Lin Yu; Danfang Yan (Molecular Genetics and Genomics, 2015)

Evaluation of pedotransfer functions for estimating saturated hydraulic conductivity in coastal salt-affected mud farmland - Rong-Jiang Yao; Jing-Song Yang; Dan-Hua Wu; Fu-Rong Li; Peng Gao; Xiang-Ping Wang (Journal of Soils and Sediments, 2015)

Activation of NOD1 by DAP contributes to myocardial ischemia/reperfusion injury via multiple signaling pathways - Hui Yang; Nan Li; Li-Na Song; Lei Wang; Cui Tian; Chao-Shu Tang; Jie Du; Hui-Hua Li; Xiao-Hong Yu; Hong-Xia Wang (Apoptosis, 2015)

The comparison of ensemble or deterministic dispersion modeling on global dispersion during Fukushima Dai-ichi nuclear accident - Li Sheng; ZhenXin Song; JiangKai Hu; Kai Lü; Hua Tong; Bing Li; QingDang Qiao (Science China Earth Sciences, 2015)

Insufficient secretion of IL-10 by Tregs compromised its control on over-activated CD4+ T effector cells in newly diagnosed adult immune thrombocytopenia patients - Feng Li; Lili Ji; Weiguang Wang; Fanli Hua; Yanxia Zhan; Shanhua Zou; Ling Yuan; Yang Ke; Zhihui Min; Dongli Song; Lihua Sun; Hao Chen; et al. (Immunologic Research, 2015)

Characterization of Arabidopsis Tubby-like proteins and redundant function of AtTLP3 and AtTLP9 in plant response to ABA and osmotic stress - Yan Bao; Wei-Meng Song; Yan-Li Jin; Chun-Mei Jiang; Yang Yang; Bei Li; Wei-Jie Huang; Hua Liu; Hong-Xia Zhang (Plant Molecular Biology, 2014)

Decreased Astroglial Monocarboxylate Transporter 4 Expression in Temporal Lobe Epilepsy - Bei Liu; Le Niu; Ming-Zhi Shen; Lei Gao; Chao Wang; Jie Li; Li-Jia Song; Ye Tao; Qiang Meng; Qian-Li Yang; Guo-Dong Gao; Hua Zhang (Molecular Neurobiology, 2014)

Expression, cloning, and IgE-binding of the full-length dust mite allergen Der f 8 - Yu-bao Cui; Ying Zhou; Nan Wang; Fei-xiang Teng; Li-li Yu; Yong-hua Bian; Jin-xia Song; Li Yang; Cheng-bo Zhang (Immunologic Research, 2014)

Research progress in China on the tropical atmospheric intraseasonal oscillation - Chongyin Li; Jian Ling; Jie Song; Jing Pan; Hua Tian; Xiong Chen (Journal of Meteorological Research, 2014)

Development of proteomic technology of shotgun and label free combined with multiple reaction monitoring to simultaneously detect southern rice black-streaked dwarf virus and rice ragged stunt virus - Zhuo Chen; Qin Guo; Bing-Hua Chen; Xiang-Yang Li; Zhen-Chao Wang; Peng He; Fei Yan; De-Yu Hu; Song Yang (VirusDisease, 2014)

Shift in abundance and structure of soil ammonia-oxidizing bacteria and archaea communities associated with four typical forest vegetations in subtropical region - Yong-Chun Li; Bu-Rong Liu; Song-Hao Li; Hua Qin; Wei-Jun Fu; Qiu-Fang Xu (Journal of Soils and Sediments, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

Down-regulation of Gli-1 inhibits hepatocellular carcinoma cell migration and invasion - Jing-Song Chen; Hua-Shu Li; Jiong-Qiang Huang; Long-Juan Zhang; Xi-Lin Chen; Qian Wang; Jian Lei; Ju-Tao Feng; Qin Liu; Xiao-Hui Huang (Molecular and Cellular Biochemistry, 2014)

A field study of the relationship between sulfide-bound metals and bioaccumulation by Limnodrilus sp. in a heavily polluted river - Feng Li; Xiang-yun Zeng; Yun-jun Yu; Chang-hua Wu; Ge Mai; Wei-wei Song; Yan-mao Wen; Zhi-peng Duan; Jia-yu Yang (Environmental Monitoring and Assessment, 2014)

AGGF1 protects from myocardial ischemia/reperfusion injury by regulating myocardial apoptosis and angiogenesis - Yu Liu; Hui Yang; Lina Song; Nan Li; Qiu-Yue Han; Cui Tian; Erhe Gao; Jie Du; Yun-Long Xia; Hui-Hua Li (Apoptosis, 2014)

Remotely sensing the ecological influences of ditches in Zoige Peatland, eastern Tibetan Plateau - Wenjiang Zhang; Qifeng Lu; Kechao Song; Guanghua Qin; Yan Wang; Xin Wang; Hongxia Li; Jun Li; Guodong Liu; Hua Li (International Journal of Remote Sensing, 2014)

Self-assembled bionanoparticles based on the Sulfolobus tengchongensis spindle-shaped virus 1 (STSV1) coat protein as a prospective bioscaffold for nanotechnological applications - Lei Song; Haina Wang; Shiwen Wang; Hua Zhang; Haolong Cong; Li Huang; Po Tien (Extremophiles, 2014)

G Protein-Coupled Estrogen Receptor–Protein Kinase A–ERK–CREB Signaling Pathway is Involved in the Regulation of Mouse Gubernaculum Testis Cells by Diethylstilbestrol - Xuan Zhang; Jian-hong Li; Shou-xing Duan; Qing-Jun Lin; Song Ke; Lian Ma; Tian-hua Huang; Xue-wu Jiang (Archives of Environmental Contamination and Toxicology, 2014)

An inactivated recombinant rabies CVS-11 virus expressing two copies of the glycoprotein elicits a higher level of neutralizing antibodies and provides better protection in mice - Xiang-Hong Xue; Xue-Xing Zheng; Hua-Lei Wang; Jin-Zhu Ma; Ling Li; Wei-Wei Gai; Tie-Cheng Wang; Song-Tao Yang; Xian-Zhu Xia (Virus Genes, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

High seroprevalence of Chlamydia infection in sows in Hunan province, subtropical China - Xiao-Xuan Zhang; Run-Cheng Li; Guo-Hua Liu; Wei Cong; Hui-Qun Song; Xing-Long Yu; Xing-Quan Zhu (Tropical Animal Health and Production, 2014)

Inhibition of 12/15 lipoxygenase by baicalein reduces myocardial ischemia/reperfusion injury via modulation of multiple signaling pathways - Lina Song; Hui Yang; Hong-Xia Wang; Cui Tian; Yu Liu; Xiang-Jun Zeng; Erhe Gao; Yu-Ming Kang; Jie Du; Hui-Hua Li (Apoptosis, 2014)

Rock physics modeling of heterogeneous carbonate reservoirs: porosity estimation and hydrocarbon detection - Hao Yu; Jing Ba; Jose Carcione; Jin-Song Li; Gang Tang; Xing-Yang Zhang; Xin-Zhen He; Hua Ouyang (Applied Geophysics, 2014)

Major QTLs reduce the deleterious effects of high temperature on rice amylose content by increasing splicing efficiency of Wx pre-mRNA - Hua Zhang; Lian Duan; Ji-Song Dai; Chang-Quan Zhang; Juan Li; Ming-Hong Gu; Qiao-Quan Liu; Ying Zhu (Theoretical and Applied Genetics, 2014)

Biphasic activation of nuclear factor kappa B and expression of p65 and c-Rel after traumatic brain injury in rats - Yang-Chun Hu; Qing Sun; Wei Li; Ding-Ding Zhang; Biao Ma; Song Li; Wei-De Li; Meng-Liang Zhou; Chun-Hua Hang (Inflammation Research, 2014)

Overweight and Obesity Associated With Increased Total Serum Calcium Level: Comparison of Cross-sectional Data in the Health Screening for Teaching Faculty - Xiao-hua Ren; Ying-shui Yao; Lian-ping He; Yue-long Jin; Wei-wei Chang; Jie Li; Yan Chen; Xiu-li Song; Hui Tang; Ling-ling Ding; Dao-xia Guo; Chao-ping Li (Biological Trace Element Research, 2013)

The discovery of 3-(1-aminoethylidene)quinoline-2, 4(1H,3H)-dione derivatives as novel PSII electron transport inhibitors - Yu-Xiu Liu; Hua-Ping Zhao; Zi-Wen Wang; Yong-Hong Li; Hai-Bin Song; Hannah Riches; David Beattie; Yu-Cheng Gu; Qing-Min Wang (Molecular Diversity, 2013)

Association of single-nucleotide polymorphisms in the STAT3 gene with autoimmune thyroid disease in Chinese individuals - Ling Xiao; Fatuma-Said Muhali; Tian-tian Cai; Rong-hua Song; Renming Hu; Xiao-hong Shi; Wen-juan Jiang; Dan-Feng Li; Shuang-tao He; Jian Xu; Jin-an Zhang (Functional & Integrative Genomics, 2013)

Association between SNPs in microRNA-machinery genes and tuberculosis susceptibility in Chinese Tibetan population - Xingbo Song; Siyue Li; MeiLang QuCuo; Yi Zhou; Xin Hu; Juan Zhou; Xiaojun Lu; Jun Wang; Wei Hua; Yuanxin Ye; Binwu Ying; Lanlan Wang (Molecular Biology Reports, 2013)

6-Hydroxydopamine promotes iron traffic in primary cultured astrocytes - Hao-Yun Zhang; Nai-Dong Wang; Ning Song; Hua-Min Xu; Li-Min Shi; Hong Jiang; Jun-Xia Xie (BioMetals, 2013)

Population persistence of a Tertiary relict tree Tetracentron sinense on the Ailao Mountains, Yunnan, China - Cindy Q. Tang; Ming-Chun Peng; Long-Yuan He; Masahiko Ohsawa; Chong-Yun Wang; Tian-Hua Xie; Wen-Shun Li; Jia-Ping Li; Hong-Yu Zhang; Yong Li; Xian-Ming Yang; Guo-Song Li (Journal of Plant Research, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

The effects of Nanos2 on Boule and Stra8 in male germline stem cells (mGSCs) - Mingzhao Li; Meng Yu; Haijing Zhu; Wencong Song; Jinlian Hua (Molecular Biology Reports, 2013)

Reduction of methylviologen-mediated oxidative stress tolerance in antisense transgenic tobacco seedlings through restricted expression of StAPX - Wei-hong Sun; Yong Wang; Hua-gang He; Xue Li; Wan Song; Bin Du; Qing-wei Meng (Journal of Zhejiang University-SCIENCE B, 2013)

Lack of association between SLCO1B1 polymorphism and the lipid-lowering effects of atorvastatin and simvastatin in Chinese individuals - Qiang Fu; Yan-Peng Li; Yuan Gao; Song-Hua Yang; Pei-Qi Lu; Min Jia; Li-Rong Zhang (European Journal of Clinical Pharmacology, 2013)

Comparative study of the interactions between ovalbumin and three alkaloids by spectrofluorimetry - Rui-qiang Wang; Yu-jing Yin; Hua Li; Yi Wang; Juan-Juan Pu; Rui Wang; Huan-jing Dou; Chuan-jun Song; Rui-yong Wang (Molecular Biology Reports, 2013)

Nitrate and nitrite content in bottled beverages by ion-pair high-performance liquid chromatography - Yang Song; Gui-Fang Deng; Xiang-Rong Xu; Yong-Hong Chen; Feng Chen; Hua-Bin Li (Food Additives & Contaminants Part B-Surveillance, 2013)

Plant-Soil Feedbacks and Soil Sickness: From Mechanisms to Application in Agriculture - Li-Feng Huang; Liu-Xia Song; Xiao-Jian Xia; Wei-Hua Mao; Kai Shi; Yan-Hong Zhou; Jing-Quan Yu (Journal of Chemical Ecology, 2013)

Isolation and characterization of a stress responsive small GTP-binding protein AhRabG3b in peanut (Arachis hypogaea L.) - Jiong-Ming Sui; Rui Li; Qian-Cheng Fan; Lin Song; Chun-Hua Zheng; Jing-Shan Wang; Li-Xian Qiao; Shan-Lin Yu (Euphytica, 2013)

Antigenic and genetic characterization of a European avian-like H1N1 swine influenza virus from a boy in China in 2011 - Xian Qi; Lunbiao Cui; Yongjun Jiao; Yuning Pan; Xihan Li; Rongqiang Zu; Xiang Huo; Bin Wu; Fengyang Tang; Yongchun Song; Minghao Zhou; Hua Wang; et al. (Archives of Virology, 2013)

Performance of four Chinese Trichogramma species as biocontrol agents of the rice striped stem borer, Chilo suppressalis, under various temperature and humidity regimes - Xiao-Hua Yuan; Li-Wei Song; Jun-Jie Zhang; Lian-Sheng Zang; Li Zhu; Chang-Chun Ruan; Guang-Zhi Sun (Journal of Pest Science, 2012)

Phylogenetic analysis of the bovine parainfluenza virus type 3 from cattle herds revealing the existence of a genotype A strain in China - Yong-Jun Wen; Xin-Chuan Shi; Feng-Xue Wang; Wei Wang; Shu-Qin Zhang; Guo Li; Ni Song; Li-Zhi Chen; Shi-Peng Cheng; Hua Wu (Virus Genes, 2012)

Physiological impacts of magnesium-deficiency in Citrus seedlings: photosynthesis, antioxidant system and carbohydrates - Gang-Hua Yang; Lin-Tong Yang; Huan-Xin Jiang; Yan Li; Ping Wang; Li-Song Chen (Trees, 2012)

Choline inhibits angiotensin II-induced cardiac hypertrophy by intracellular calcium signal and p38 MAPK pathway - Shu Wang; Hong-mei Han; Zhen-wei Pan; Peng-zhou Hang; Li-hua Sun; Ya-nan Jiang; Hao-xin Song; Zhi-min Du; Yan Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Holocene vegetation and climate history at Haligu on the Jade Dragon Snow Mountain, Yunnan, SW China - Xiao-Yan Song; Yi-Feng Yao; A. H. Wortley; K. N. Paudayal; Shao-Hua Yang; Cheng-Sen Li; S. Blackmore (Climatic Change, 2012)

Molecular characterization and phylogenetic analysis of porcine epidemic diarrhea virus (PEDV) field strains in south China - Zhi-Li Li; Ling Zhu; Jing-Yun Ma; Qing-Feng Zhou; Yan-Hua Song; Bao-Li Sun; Rui-Ai Chen; Qing-Mei Xie; Ying-Zuo Bee (Virus Genes, 2012)

3-Nitro-naphthalimide and nitrogen mustard conjugate NNM-25 induces hepatocellular carcinoma apoptosis via PARP-1/p53 pathway - Song-qiang Xie; Ya-hong Zhang; Qian Li; Feng-hua Xu; Jiu-wang Miao; Jin Zhao; Chao-jie Wang (Apoptosis, 2012)

SK channels modulate the excitability and firing precision of projection neurons in the robust nucleus of the arcopallium in adult male zebra finches - Guo-Qiang Hou; Xuan Pan; Cong-Shu Liao; Song-Hua Wang; Dong-Feng Li (Neuroscience Bulletin, 2012)

Polymorphisms in luteinizing hormone receptor and hypothalamic gonadotropin-releasing hormone genes and their effects on sperm quality traits in Chinese Holstein bulls - Li-Ping Sun; Qing-Zhi Du; Ya-Pan Song; Jun-Na Yu; Shu-Juan Wang; Lei Sang; Luo-Wen Song; Yao-Min Yue; Yu-Ze Lian; Sheng-Li Zhang; Guo-Hua Hua; Shu-Jun Zhang; et al. (Molecular Biology Reports, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Molecular cloning and characterization of the promoter of SmGGPPs and its expression pattern in Salvia miltiorrhiza - Wenping Hua; Jie Song; Cuiqin Li; Zhezhi Wang (Molecular Biology Reports, 2012)

Characterization of the expression profiles of calpastatin (CAST) gene in chicken - Zeng-Rong Zhang; Xiao-Song Jiang; Hua-Rui Du; Qing Zhu; Xiao-Cheng Li; Chao-Wu Yang; Yi-Ping Liu (Molecular Biology Reports, 2012)

Lysosomal membrane permeabilization is involved in curcumin-induced apoptosis of A549 lung carcinoma cells - Qing-Yong Chen; Jian-Guo Shi; Qing-Hua Yao; De-Min Jiao; Yan-Yi Wang; Hui-Zhen Hu; Yu-Quan Wu; Jia Song; Jie Yan; Li-Jun Wu (Molecular and Cellular Biochemistry, 2012)

Analysis of Lanthanide-Induced Conformational Change of the C-Terminal Domain on Centrin - Ya-Qin Zhao; Jun Yan; Li Song; Ya-Nan Feng; Ai-Hua Liang; Bin-Sheng Yang (Journal of Fluorescence, 2012)

Seed size is determined by the combinations of the genes controlling different seed characteristics in rice - Song Yan; Guihua Zou; Sujuan Li; Hua Wang; Heqin Liu; Guowei Zhai; Peng Guo; Hongmiao Song; Changjie Yan; Yuezhi Tao (Theoretical and Applied Genetics, 2011)

A new QTL for resistance to Fusarium ear rot in maize - Zhi-Min Li; Jun-Qiang Ding; Rui-Xia Wang; Jia-Fa Chen; Xiao-Dong Sun; Wei Chen; Wei-Bin Song; Hua-Fang Dong; Xiao-Dong Dai; Zong-Liang Xia; Jian-Yu Wu (Journal of Applied Genetics, 2011)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Noradrenaline regulates substance P release from rat dorsal root ganglion neurons in vitro - Yan-Jie Wang; Xing-Fu Li; Feng Ding; Qiang Shu; Li-Jun Song; Xiao Yu; Hua-Xiang Liu (Neuroscience Bulletin, 2011)

Prevalence, intensity and associated factor analysis of Tropilaelaps mercedesae infesting Apis mellifera in China - Qi Hua Luo; Ting Zhou; Ping Li Dai; Huai Lei Song; Yan Yan Wu; Qiang Wang (Experimental and Applied Acarology, 2011)

A novel procedure for acid-catalysed K2FeO4 oxidation of benzyl alcohol in organic phase - Hua Song; Zheng Guang Li; Bao Hui Wang (Environmental Chemistry Letters, 2011)

Neuroprotection of Interleukin-6 Against NMDA-Induced Apoptosis and Its Signal-Transduction Mechanisms - Zhan Liu; Yi-Hua Qiu; Bing Li; Song-Hua Ma; Yu-Ping Peng (Neurotoxicity Research, 2011)

The complete mitochondrial genomes of three cestode species of Taenia infecting animals and humans - Guo-Hua Liu; Rui-Qing Lin; Ming-Wei Li; Wei Liu; Yi Liu; Zi-Guo Yuan; Hui-Qun Song; Guang-Hui Zhao; Kou-Xing Zhang; Xing-Quan Zhu (Molecular Biology Reports, 2011)

Construction of a Tn5-Tagged Mutant Library of Xanthomonas oryzae pv. oryzicola as An Invaluable Resource for Functional Genomics - Hua-Song Zou; Liang Yuan; Wei Guo; Yu-Rong Li; Yi-Zhou Che; Li-Fang Zou; Gong-You Chen (Current Microbiology, 2011)

Analysis of bacterial communities in rhizosphere soil of healthy and diseased cotton (Gossypium sp.) at different plant growth stages - Yan Zhang; Bing-Hai Du; Zhi-gang Jin; Zheng-hua Li; Hong-ning Song; Yan-Qin Ding (Plant and Soil, 2011)

Silica-supported sulfonic acid-functionalized ionic liquid coated with [bmim][PF6] as a scavenger for the synthesis of amides - Li-Qin Kang; Yue-Qin Cai; Yan-Qing Peng; Xi-Li Ying; Gong-Hua Song (Molecular Diversity, 2011)

The Cucumber Lateral Suppressor Gene (CLS) Is Functionally Associated with Axillary Meristem Initiation - Li-Hua Yuan; Jun-Song Pan; Gang Wang; Jun Zhu; Wei-Wei Zhang; Zheng Li; Huan-Le He; Zhong-Nan Yang; Run Cai; Li-Huang Zhu (Plant Molecular Biology Reporter, 2010)

Investigation on Metal Pollution in the Sediment of Chongqing Segment of Yangtse River - Cai-hong Luo; Qing-mei Wu; Song Li; Hong Yang; Chen-hua Zhong (Bulletin of Environmental Contamination and Toxicology, 2010)

Evaluation and Structure-Activity Relationship Study of Acute Toxicity of Naphthoquinones to Photobacterium phosphoreum, Photobacterium T3B - Feng Ding; Jing Guo; Zhen Li; Li Ying Li; Jin Yang Zhang; Jin Hua Zhang; Jie Lian; Wen Hua Song; Lin Zhu (Bulletin of Environmental Contamination and Toxicology, 2010)

Assessment of candidate plant DNA barcodes using the Rutaceae family - Kun Luo; ShiLin Chen; KeLi Chen; JingYuan Song; Hui Yao; Xinye Ma; YingJie Zhu; XiaoHui Pang; Hua Yu; XiWen Li; Zhen Liu (Science China Life Sciences, 2010)

Recombinant adenovirus-mediated expression of GHS-R1a in HEK 293 cells - Li Liu; Hua-Min Xu; Hong Jiang; Jun Wang; Ning Song; Jun-Xia Xie (Neuroscience Bulletin, 2010)

The effects of mesenchymal stem cells on c-kit up-regulation and cell-cycle re-entry of neonatal cardiomyocytes are mediated by activation of insulin-like growth factor 1 receptor - Xi-Yong Yu; Yong-Jian Geng; Xiao-Hong Li; Qiu-Xiong Lin; Zhi-Xin Shan; Shu-Guang Lin; Yao-Hua Song; Yangxin Li (Molecular and Cellular Biochemistry, 2009)

Valsartan preconditioning protects against myocardial ischemia–reperfusion injury through TLR4/NF-κB signaling pathway - Jian Yang; Hong Jiang; Jun Yang; Jia-Wang Ding; Li-Hua Chen; Song Li; Xiao-Dong Zhang (Molecular and Cellular Biochemistry, 2009)

Prevalence, genetic diversity, and antimicrobial susceptibility profiles of Staphylococcus aureus isolated from bovine mastitis in Zhejiang Province, China - Jian-ping Li; Hai-jian Zhou; Lin Yuan; Ting He; Song-hua Hu (Journal of Zhejiang University-SCIENCE B, 2009)

Rural wastewater irrigation and nitrogen removal by the paddy wetland system in the Tai Lake region of China - Song Li; Hua Li; Xingqiang Liang; Yingxu Chen; Zhihong Cao; Zhihong Xu (Journal of Soils and Sediments, 2009)

Rosmarinic Acid Inhibits 6-OHDA-induced Neurotoxicity by Anti-oxidation in MES23.5 Cells - Pei Ren; Hong Jiang; Ronggui Li; Jun Wang; Ning Song; Hua-Min Xu; Jun-Xia Xie (Journal of Molecular Neuroscience, 2009)

Improvement of chloroperoxidase stability by covalent immobilization on chitosan membranes - Li-Hua Zhang; Chao-Hong Bai; Ying-Song Wang; Yu-Cheng Jiang; Man-Cheng Hu; Shu-Ni Li; Quan-Guo Zhai (Biotechnology Letters, 2009)

Aggregation Pheromone of the Qinghai Spruce Bark Beetle, Ips nitidus Eggers - Qing-He Zhang; Jian-Hai Ma; Feng-Yu Zhao; Li-Wen Song; Jiang-Hua Sun (Journal of Chemical Ecology, 2009)

Gastric carcinoma with osteoclast-like giant cells: a case report and review of the literature - Li-duan Zheng; Xiu-ping Yang; Hua-xiong Pan; Xiu Nie; Jun He; Qing Lv; Qiang-song Tong (Journal of Zhejiang University-SCIENCE B, 2009)

Notch signaling regulates the FOXP3 promoter through RBP-J- and Hes1-dependent mechanisms - Hai-Feng Ou-Yang; Hong-Wei Zhang; Chang-Gui Wu; Ping Zhang; Jian Zhang; Jun-Chang Li; Li-Hong Hou; Fei He; Xin-Yu Ti; Li-Qiang Song; Su-Zhen Zhang; Lei Feng; et al. (Molecular and Cellular Biochemistry, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

A rapid and accurate 3-(4,5-dimethyl thiazol-2-yl)-2,5-diphenyl tetrazolium bromide colorimetric assay for quantification of bacteriocins with nisin as an example - Fang Wang; Li-ting Cao; Song-hua Hu (Journal of Zhejiang University-SCIENCE B, 2007)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

Comparative analysis of telomeric restriction fragment lengths in different tissues of Ginkgo biloba trees of different age - Di Liu; Nan Qiao; Han Song; Xin Hua; Juan Du; Hai Lu; Fenglan Li (Journal of Plant Research, 2007)

Comparison of genetic variation in populations of wild rice, Oryza rufipogon, plants and their soil seed banks - Gui-hua Liu; Li-ming Luo; Bin Wang; Wei Li; Zhiping Song (Conservation Genetics, 2006)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Invasive alien plants in China: role of clonality and geographical origin - Jian Liu; Ming Dong; Shi Li Miao; Zhen Yu Li; Ming Hua Song; Ren Qing Wang (Biological Invasions, 2006)

Molecular analysis of early rice stamen development using organ-specific gene expression profiling - Xiao-Chun Lu; Hua-Qin Gong; Mo-Li Huang; Su-Lan Bai; Yang-Bo He; Xizeng Mao; Zhi Geng; Song-Gang Li; Liping Wei; Jie-Shuai Yuwen; Zhi-Hong Xu; Shu-Nong Bai (Plant Molecular Biology, 2006)

Heterologous Expression and Purification of Recombinant Allophycocyanin in Marine Streptomyces sp. Isolate M097 - Yan-Hua Hou; Song Qin; You-Xun Li; Fu-Chao Li; Huan-Zhang Xia; Fang-Qing Zhao (World Journal of Microbiology and Biotechnology, 2006)

Tissue distribution of the secretory protein, SPLUNC1, in the human fetus - Hou-De Zhou; Song-Qin Fan; Jin Zhao; Dong-Hai Huang; Ming Zhou; Hua-Ying Liu; Zhao-Yang Zeng; Yi-Xing Yang; He Huang; Xiao-Ling Li; Shou-Rong Shen; Gui-Yuan Li (Histochemistry and Cell Biology, 2006)

Green Fluorescent Protein Labeling Escherichia coli TG1 Confirms Intestinal Bacterial Translocation in a Rat Model of Chemotherapy - Desheng Song; Bin Shi; Hua Xue; Yousheng Li; Baojun Yu; Zhe Xu; Fukun Liu; Jieshou Li (Current Microbiology, 2006)

Effects of water table and nitrogen addition on CO2 emission from wetland soil - Ji-song Yang; Jing-shuang Liu; Jun-bao Yu; Jin-da Wang; Sheng-jin Qin; Xin-hua Li (Chinese Geographical Science, 2005)

Activation of the WUS Gene Induces Ectopic Initiation of Floral Meristems on Mature Stem Surface in Arabidopsis thaliana - Yun-Yuan Xu; Xiao-Min Wang; Jia Li; Ju-Hua Li; Jin-Song Wu; John C. Walker; Zhi-Hong Xu; Kang Chong (Plant Molecular Biology, 2005)

Activation of the WUS gene induces ectopic initiation of floral meristems on mature stem surface in Arabidopsis thaliana - Yun-Yuan Xu; Xiao-Min Wang; Jia Li; Jun-Hua Li; Jin-Song Wu; John C. Walker; Zhi-Hong Xu; Kang Chong (Plant Molecular Biology, 2005)

Evaluation of genetic diversity and germ plasm identification of 44 species, clones, and cultivars from 5 sections of the genusPopulus based on amplified fragment length polymorphism analysis - Chun Jiang Zhou; Hong Zhu Song; Jin Hua Li; Jian Wei Sun; Min De Jin; Qi Wen Zhang; Bin Wang (Plant Molecular Biology Reporter, 2005)

Application of swat model in the upstream watershed of the Luohe River - Xue-song Zhang; Fang-hua Hao; Hong-guang Cheng; Dao-feng Li (Chinese Geographical Science, 2003)

(R)-Oxynitrilase-catalysed synthesis of chiral silicon-containing aliphatic (R)-ketone-cyanohydrins - Ning Li; Min-Hua Zong; Chen Liu; Hua-Song Peng; Hua-Chang Wu (Biotechnology Letters, 2003)

A study on desertification of west Jilin Province based on remote sensing and GIS techniques - Jin-hua Zhu; Jin-song Li (Chinese Geographical Science, 2002)

Characteristics of water transformation and its effects on environment in the arid region - Xin Li; Yu-dong Song; Fu-hua Nian (Chinese Geographical Science, 2000)